Cathode current collector and electrolytic capacitor
By constructing a dense organic conductive layer and porous layer structure on the cathode current collector and combining the inorganic conductive layer, the problem of poor adhesion between the cathode current collector and the solid electrolyte layer is solved, low ESR and high durability are achieved, and capacitors are improved performance.
Patent Information
- Application Number
- CN202380010597.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-13
- Publication Date
- 2024-12-13
AI Technical Summary
In the prior art, the poor adhesion between the cathode current collector and the solid electrolyte layer leads to an increase in contact resistance, affecting the ESR and reliability of the capacitor, especially in high frequency regions, and the structure of the organic conductive layer is not suitable enough to prevent electrolysis. Liquid penetration leads to poor initial ESR and long-life reliability.
A cathode matrix formed by valve metal is adopted, with an oxide layer and a dense organic conductive layer on the surface, which is composed of a dense layer and a porous layer, and an inorganic conductive layer is provided between the oxide layer and the organic conductive layer to ensure adhesion. and prevent electrolyte penetration, optimize the thickness and porosity of the organic conductive layer.
It significantly reduces the ESR of the capacitor in the high frequency region, improves durability and reliability, ensures the full adhesion between the cathode current collector and the solid electrolyte layer, reduces the penetration of the electrolyte solution, and extends the service life of the electrode.
Smart Images

Figure CN119137700A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a cathode current collector and an electrolytic capacitor. Background Art
[0002] In recent years, with the miniaturization and high speed of electronic devices, in the field of electrolytic capacitors using solid electrolytes, the demand for small and large-capacity capacitors with low equivalent series resistance (hereinafter referred to as "ESR") in the high-frequency region has been rising. In electrolytic capacitors using solid electrolytes, a cathode collector is used, which has: a cathode substrate formed of a valve metal, and an oxide layer formed of an oxide of the valve metal disposed on the surface of the cathode substrate, and an inorganic conductive layer containing an inorganic conductive material is further disposed on the surface as needed. There is a contact resistance between the surface of the cathode collector and the electrolyte component, and this contact resistance will have a very large impact on the ESR of the capacitor.
[0003] Usually, when forming a solid electrolyte layer, a dispersion containing a conductive polymer dispersion is mostly used. The dispersion, in particular, causes a problem of reducing the adhesion between the solid electrolyte layer and the cathode collector, thereby increasing the contact resistance. In particular, in a hybrid electrolytic capacitor, the solid electrolyte layer formed using the dispersion is easy to retain the electrolyte, so the electrolyte easily penetrates between the solid electrolyte layer and the cathode collector, so the adhesion is reduced and the contact resistance is increased.
[0004] For example, in Patent Document 1, regarding a cathode collector having an inorganic conductive layer disposed on the surface of a cathode substrate, it is proposed to improve the adhesion between the cathode collector and the solid electrolyte layer by roughening the surface of the cathode substrate before the inorganic conductive layer is disposed. In accordance with the roughened structure formed on the surface of the cathode substrate, bumps and depressions are also formed on the surface of the inorganic conductive layer. The area of the concave portion on the surface of the inorganic conductive layer will not contact the solid electrolyte layer. The electrolyte used as an electrolyte of the capacitor is guided to the area of the concave portion on the surface of the inorganic conductive layer, so that the adhesion between the cathode collector and the solid electrolyte layer is improved. In addition, the hybrid electrolytic capacitor obtained using such a cathode collector has a reduced initial ESR, and the increase in ESR after the no-load test is also suppressed.
[0005] In addition, for example, in Patent Document 2, regarding a cathode collector in which an oxide layer and an inorganic conductive layer are sequentially arranged on the surface of a cathode substrate, it is proposed that an organic conductive layer is also arranged on the surface of the inorganic conductive layer to improve the adhesion between the cathode collector and the solid electrolyte layer. By arranging an organic conductive layer with low impregnation of the electrolyte on the surface of the inorganic conductive layer, almost all of the electrolyte used as an electrolyte of the capacitor is retained in the solid electrolyte layer. As a result, the adhesion between the cathode collector and the solid electrolyte layer is improved. Furthermore, the hybrid electrolytic capacitor obtained using such a cathode collector has a reduced initial ESR, and the increase in ESR after the load test is also suppressed.
[0006] Furthermore, for example, Patent Document 3 proposes that, in a solid electrolytic capacitor, impedance in a high frequency region is reduced by using a conductive separator, and impedance is further reduced by forming an organic conductive layer on the surface of a cathode current collector.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: International Publication No. 2016 / 174806
[0010] Patent Document 2: International Publication No. 2021 / 125182
[0011] Patent Document 3: Japanese Patent Application Laid-Open No. 7-283086 Summary of the invention
[0012] Technical problem to be solved by the invention
[0013] As described in patent document 1, by using a cathode current collector provided with an inorganic conductive layer on the cathode substrate after roughening, the adhesion with the solid electrolyte layer can be improved to some extent. However, even if the electrolyte is guided to the region of the recessed portion of the inorganic conductive layer surface where the solid electrolyte layer and the inorganic conductive layer are not in contact, as described in patent document 1, the solid electrolyte layer formed using a dispersion is easy to retain the electrolyte. Therefore, the electrolyte easily enters between the solid electrolyte layer and the cathode current collector, and the problem of poor adhesion is not fundamentally improved.
[0014] As shown in Patent Document 2, by giving an organic conductive layer to the surface of the inorganic conductive layer, the adhesion between the cathode collector and the solid electrolyte layer is improved to some extent. However, after in-depth research, it was found that by making the structure of the organic conductive layer more suitable, the characteristics can be further improved. That is, Patent Document 2 believes that the organic conductive layer is preferably a dense layer with a density within a specified range. However, even if such a dense organic conductive layer is combined with a solid electrolyte layer that is easy to retain the electrolyte, the adhesion between the cathode collector and the solid electrolyte layer will still be reduced because the electrolyte will penetrate into the interface between the cathode collector and the solid electrolyte layer, and the problem of contact resistance is not fully solved. The electrolyte penetrates toward the interface between the cathode collector and the solid electrolyte layer, which will especially deteriorate the high reliability of long life. In addition, in Patent Document 2, the thickness of the organic conductive layer is usually set to 1 to 2000 nm. However, with such a thin organic conductive layer, it is impossible to fully prevent the electrolyte from penetrating into the interface between the inorganic conductive layer and the organic conductive layer, and the adhesion between the inorganic conductive layer and the organic conductive layer will be reduced. The electrolyte penetrates into the interface between the inorganic conductive layer and the organic conductive layer, which particularly deteriorates the initial ESR. Therefore, in Patent Document 2, neither the adhesion between the cathode collector and the solid electrolyte layer, nor the adhesion between the inorganic conductive layer and the organic conductive layer in the cathode collector can be said to be sufficient, and the initial ESR and high reliability of long life are insufficient.
[0015] It should be noted that both Patent Documents 1 and 2 relate to hybrid electrolytic capacitors using both solid electrolytes and electrolytes as electrolyte components, but the adhesion between the cathode collector and the solid electrolyte layer is also a problem in solid electrolytic capacitors that do not use electrolytes as the electrolyte components of capacitors. For example, Patent Document 3 shows that the organic conductive layer formed on the surface of the cathode collector brings about an impedance reduction effect, but the specific structure of the organic conductive layer at this time is not mentioned at all. However, as mentioned above, after in-depth research, it was found that by making the structure of the organic conductive layer more suitable, the characteristics can be further improved.
[0016] In the above-mentioned prior art, there is still room for improvement in the problem of contact resistance, that is, (1) there is still room for improvement in the rate of change of ESR over time caused by the deterioration of the tightness between the cathode collector and the solid electrolyte layer, and (2) there is also room for improvement in the initial value of ESR caused by the deterioration of the tightness within the cathode collector (the tightness of the oxide layer provided on the surface of the cathode substrate and the organic conductive layer, or the tightness of the inorganic conductive layer provided on the surface of the oxide layer and the organic conductive layer).
[0017] It should be noted that in an electrolytic capacitor including a cathode current collector using a cathode substrate formed of a valve metal, the solid electrolyte layer used in the electrolytic capacitor includes a solid electrolyte layer formed by a dispersion liquid including a dispersion formed of conductive polymer particles and a dispersion medium, and a solid electrolyte layer formed by chemical polymerization using a monomer and an oxidant. In chemical polymerization, during chemical polymerization of the monomer and the oxidant, the surface of the cathode current collector becomes acidic and is damaged, which becomes a problem.
[0018] Therefore, one of the objects of the present invention is to provide a cathode current collector and an electrolytic capacitor that can improve at least one of the above-mentioned problems of contact resistance and damage on the surface of the cathode current collector.
[0019] Solutions to technical problems
[0020] The cathode collector provided by the first aspect of the present invention comprises: a cathode substrate formed of a valve metal; an oxide layer formed of an oxide of the valve metal arranged on the surface of the cathode substrate; and an organic conductive layer containing a conductive polymer arranged on the surface of the oxide layer, wherein the organic conductive layer is composed of a dense layer arranged on the surface of the oxide layer and a porous layer arranged on the surface of the dense layer.
[0021] The cathode collector provided by the second aspect of the present invention comprises: a cathode substrate formed by a valve metal; an oxide layer formed by an oxide of the valve metal arranged on the surface of the cathode substrate; and an organic conductive layer containing a conductive polymer arranged on the surface of the oxide layer, wherein the organic conductive layer is composed of a dense layer arranged on the surface of the oxide layer, and the thickness of the organic conductive layer is greater than 2μm and less than 22μm.
[0022] In the cathode current collector provided in the first and second aspects of the present invention, an inorganic conductive layer containing an inorganic conductive material is further provided between the oxide layer and the organic conductive layer, and the dense layer is provided on the surface of the inorganic conductive layer.
[0023] In the cathode current collector provided in the first aspect and the second aspect of the present invention, the surface of the cathode substrate may be smooth.
[0024] In the cathode current collector provided in the first aspect of the present invention, the thickness of the porous layer may be 2 μm or more and 25 μm or less.
[0025] In the cathode current collector provided in the first aspect of the present invention, the thickness of the dense layer may be greater than or equal to 0.02 μm and less than 15 μm.
[0026] In the cathode current collector provided in the first aspect of the present invention, the porosity of the porous layer may be 0.1 or more and 0.7 or less.
[0027] In the cathode current collector provided in the first aspect and the second aspect of the present invention, the organic conductive layer may be an electrolytic polymer film.
[0028] In the cathode current collector provided in the first aspect and the second aspect of the present invention, the conductive polymer may be poly(3,4-ethylenedioxythiophene).
[0029] The electrolytic capacitor provided by the third aspect of the present invention contains at least a solid electrolyte as an electrolyte component and uses the cathode current collector provided by the present invention.
[0030] The electrolytic capacitor provided in the fourth aspect of the present invention is an electrolytic capacitor having a cathode collector and at least a solid electrolyte as an electrolyte component, wherein the cathode collector has: a cathode substrate formed of a valve metal; an oxide layer formed of an oxide of the valve metal arranged on the surface of the cathode substrate; and an organic conductive layer containing a conductive polymer arranged on the surface of the oxide layer, wherein the organic conductive layer is tightly arranged on the surface of the oxide layer, and the thickness of the organic conductive layer is greater than 2μm and less than 22μm.
[0031] In the electrolytic capacitor provided by the fourth aspect of the present invention, an inorganic conductive layer including an inorganic conductive material is further provided between the oxide layer and the organic conductive layer, and the organic conductive layer is provided in close contact with the surface of the inorganic conductive layer.
[0032] In the electrolytic capacitor provided by the fourth aspect of the present invention, the surface of the cathode substrate may be smooth.
[0033] In the electrolytic capacitor provided in the fourth aspect of the present invention, the organic conductive layer may be an electrolytic polymer film.
[0034] In the electrolytic capacitor provided in the fourth aspect of the present invention, the conductive polymer may be poly(3,4-ethylenedioxythiophene).
[0035] The electrolytic capacitor provided in the third and fourth aspects of the present invention may further contain an electrolytic solution as an electrolyte component.
[0036] Effects of the Invention
[0037] According to the cathode collector and electrolytic capacitor of various aspects of the present invention, the problem of contact resistance of at least one prior art can be improved. In particular, the cathode collector and electrolytic capacitor of various aspects of the present invention can achieve low ESR and high durability in the high frequency region. Here, although high frequency has no clear definition, but represents different frequency ranges according to the application field, in the field related to electricity, high frequency sometimes represents a frequency range from several kHz to tens of MHz. In the field of specific capacitors, high frequency sometimes represents a frequency range from several kHz to hundreds of kHz, but is not limited to this. Various aspects of the present invention, especially in the case of using a solid electrolyte layer using a dispersion liquid, can also play an effect in the case of using a solid electrolyte layer using chemical polymerization. That is, according to the cathode collector and electrolytic capacitor of various aspects of the present invention, by forming an organic conductive layer that hinders the penetration of the polymerization liquid of monomers and oxidants on the surface of the cathode collector, it is possible to suppress the damage to the surface of the cathode collector during chemical polymerization, and it is possible to achieve low ESR and high durability. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 This is a cross-sectional view showing the layer structure of the cathode current collector according to one embodiment of the first aspect of the present invention.
[0039] Figure 2 This is a cross-sectional view showing the layer structure of a cathode current collector according to another embodiment of the first aspect of the present invention.
[0040] Figure 3 This is a cross-sectional view showing the layer structure of a cathode current collector according to one embodiment of the second aspect of the present invention.
[0041] Figure 4 It is a cross-sectional view showing the layer structure of the cathode current collector in the electrolytic capacitor according to one embodiment of the third aspect of the present invention.
[0042] Figure 5 This is an enlarged cross-sectional photograph of a part of the organic conductive layer in the cathode current collector according to another embodiment of the first aspect of the present invention. DETAILED DESCRIPTION
[0043] Hereinafter, the cathode current collector and the electrolytic capacitor of the present invention will be described with reference to the accompanying drawings. It should be noted that the pictures are used to illustrate the present invention, but the present invention is not limited to the contents of the pictures. In addition, the embodiments and examples disclosed this time are examples of all aspects, but the scope of the present invention is not limited to these contents. Features equivalent to the scope of the claims and all changes within the scope are included in the scope of the present invention.
[0044] 1. Regarding cathode current collectors 7, 8 and 10
[0045] The structure of the cathode current collector of one embodiment of the first aspect of the present invention is Figure 1 Schematically shown in . The cathode current collector 7 comprises: a cathode substrate 1 formed of a valve metal; an oxide layer 2 provided on the surface of the cathode substrate 1 and formed of an oxide of the valve metal constituting the cathode substrate 1; and an organic conductive layer 6 comprising a conductive polymer provided on the surface of the oxide layer 2, wherein the organic conductive layer 6 is composed of a dense layer 4 provided on the surface of the oxide layer 2 and a porous layer 5 provided on the surface of the dense layer 4. The porous layer 5 is a layer in which a plurality of pores are observed in the thickness direction. The dense layer 4 is a dense layer having fewer pores than the porous layer 5. The dense layer 4 is a layer having almost no pores. The specific structures of the dense layer 4 and the porous layer 5 and the determination of the presence or absence of these layers are described in detail below.
[0046] Here, by providing the dense layer 4 on the surface of the oxide layer 2 in contact with the organic conductive layer 6, the adhesion between the oxide layer 2 and the organic conductive layer 6 can be ensured. This is because, by having the characteristic of the dense layer 4 being continuously present between the oxide layer 2, the number of contact points between the oxide layer 2 and the organic conductive layer 6 (dense layer 4) can be increased, and the entry of substances that deteriorate the adhesion into the space between the oxide layer 2 and the organic conductive layer 6 can be reduced. In addition, by ensuring the adhesion between the oxide layer 2 and the organic conductive layer 6, the contact resistance can be reduced, and the initial value of the ESR can be reduced.
[0047] In addition, by providing a porous layer 5 on the surface of the dense layer 4, that is, by providing a porous layer 5 on the portion on the side where the organic conductive layer 6 contacts the solid electrolyte layer, the adhesion between the organic conductive layer 6 and the solid electrolyte layer can be ensured. It is believed that this is due to the anchoring effect that the dispersion of the conductive polymer enters the porous layer 5 when the solid electrolyte layer is formed, and the organic conductive layer 6 and the solid electrolyte layer are integrated. By ensuring the adhesion between the organic conductive layer 6 and the solid electrolyte layer, the increase in contact resistance caused by the peeling of the solid electrolyte layer can be suppressed, the adhesion between the cathode collector 7 and the solid electrolyte layer can become sufficient, and the time-dependent ESR change rate can be reduced.
[0048] The structure of the cathode current collector of another embodiment of the first aspect of the present invention is Figure 2 In addition, the cross-sectional photo is shown in Figure 5The cathode current collector 8 comprises: a cathode substrate 1 formed of a valve metal; an oxide layer 2 formed of an oxide of the valve metal constituting the cathode substrate 1 and disposed on the surface of the cathode substrate 1; an inorganic conductive layer 3 disposed on the surface of the oxide layer 2; and an organic conductive layer 6 comprising a conductive polymer disposed on the surface of the inorganic conductive layer 3, wherein the organic conductive layer 6 comprises a dense layer 4 disposed on the surface of the oxide layer 2 and a porous layer 5 disposed on the surface of the dense layer 4.
[0049] Here, by providing the dense layer 4 on the surface of the inorganic conductive layer 3 in contact with the organic conductive layer 6, the adhesion between the inorganic conductive layer 3 and the organic conductive layer 6 can be ensured. This is because, by having the feature that the dense layer 4 continuously exists between the inorganic conductive layer 3 as described above, the number of contact points between the inorganic conductive layer 3 and the organic conductive layer 6 (dense layer 4) can be increased, and the substances that deteriorate the adhesion can be reduced from entering the space between the inorganic conductive layer 3 and the organic conductive layer 6. In addition, by ensuring the adhesion between the inorganic conductive layer 3 and the organic conductive layer 6, the contact resistance can be reduced, and the initial value of ESR can be reduced.
[0050] In addition, by providing a porous layer 5 on the surface of the dense layer 4, that is, providing a porous layer on the side where the organic conductive layer 6 contacts the solid electrolyte layer, the adhesion between the organic conductive layer 6 and the solid electrolyte layer can be ensured. This is also due to the anchoring effect described above, and by making the adhesion between the cathode collector 8 and the solid electrolyte layer sufficient, the time-dependent ESR change rate can be reduced.
[0051] Generally, when a solid electrolyte layer using a dispersion of a conductive polymer is used, the problem of contact resistance caused by the poor adhesion between the cathode collector and the solid electrolyte layer and / or the poor adhesion inside the cathode collector may occur. In contrast, in the cathode collectors 7 and 8 of the embodiments of the present invention, the problem of contact resistance can be at least partially improved by providing an organic conductive layer 6 consisting of a multilayer structure having a dense layer 4 and a porous layer 5 in a manner that forms a structure suitable for each interface. More specifically, by providing a dense layer 4 on the surface of the oxide layer 2 or the inorganic conductive layer 3, the adhesion inside the cathode collector (the adhesion between the oxide layer provided on the surface of the cathode substrate and the organic conductive layer, or the adhesion between the inorganic conductive layer provided on the surface of the oxide layer and the organic conductive layer) can be improved, and the initial value of ESR can be reduced. In addition, by providing a porous layer 5 on the surface of the dense layer 4, the adhesion between the cathode collector and the solid electrolyte layer can be improved, and the rate of change of ESR over time can be suppressed.
[0052] The structure of the cathode current collector of one embodiment of the second aspect of the present invention is Figure 3Schematically shown in FIG. 1 . The cathode current collector 10 comprises: a cathode substrate 1 formed of a valve metal; an oxide layer 2 formed of an oxide of a valve metal constituting the cathode substrate 1 and disposed on the surface of the cathode substrate 1; an inorganic conductive layer 3 disposed on the surface of the oxide layer 2; and an organic conductive layer 9 comprising a conductive polymer disposed on the surface of the inorganic conductive layer 3, wherein the organic conductive layer 9 is formed of a dense layer disposed on the surface of the inorganic conductive layer 3, and the thickness of the organic conductive layer 9 is greater than 2 μm and is less than 22 μm.
[0053] Here, by providing a dense layer as the organic conductive layer 9 on the surface of the inorganic conductive layer 3 in contact with the organic conductive layer 9, the dispersion of the conductive polymer can be prevented from penetrating into the interface between the inorganic conductive layer 3 and the organic conductive layer 9. Furthermore, by setting the thickness of the organic conductive layer 9 to be greater than 2 μm, the electrolyte can be sufficiently prevented from penetrating into the interface between the inorganic conductive layer 3 and the organic conductive layer 9, the adhesion can be ensured, the initial value of the ESR can be sufficiently reduced, and the problem of contact resistance can be solved. On the other hand, by setting the thickness of the organic conductive layer 9 to be less than 22 μm, the increase in the ESR caused by the increase in the distance between the capacitor electrodes can be suppressed.
[0054] It should be noted that although Figure 3 An inorganic conductive layer 3 is also provided, but no Figure 3 The cathode current collector of the inorganic conductive layer 3 in the present invention is also included in the present invention. In this case, the relationship between the inorganic conductive layer 3 and the organic conductive layer 9 is converted into the relationship between the oxide layer 2 and the organic conductive layer 9. That is, when the inorganic conductive layer 3 is not provided, the organic conductive layer 9 (dense layer) is provided on the surface of the oxide layer 2.
[0055] (1) Regarding cathode substrate 1
[0056] The cathode substrate 1 is not particularly limited, and a substrate formed of a valve metal used as a cathode substrate in an existing electrolytic capacitor can be used. For example, a foil formed of a valve metal such as aluminum, tantalum, niobium, and titanium can be used as the cathode substrate 1, and aluminum foil is particularly preferred. Here, the foil is not limited, and can refer to a sheet-like member with a thickness of 200 μm or less.
[0057] As the cathode substrate 1, any one of a substrate subjected to a roughening treatment such as etching and a substrate that is not subjected to a roughening treatment and remains smooth can be used. In addition, when etching is performed as a roughening treatment, it can be a known chemical etching method or a known electrolytic etching method. Furthermore, the holes formed by etching can be tunnel-shaped holes, sponge-shaped holes, or a combination thereof.
[0058] However, when a roughened cathode substrate is used, the electrolyte residue during electrolytic polymerization is likely to remain in the etched structure, but in the case of a smooth cathode substrate, it is easy to remove by cleaning and the residue is unlikely to remain. The residue is related to performance degradation, so a smooth cathode substrate is preferred.
[0059] It should be noted that the term "smooth" here refers to a surface state that has not been roughened by etching or other treatments as described above. Although the surface can be completely flat, it does not necessarily have to be completely flat. "Smooth" also includes the situation where small roughness or undulations such as unavoidable rolling textures or scratches slightly generated in the foil base manufacturing process such as rolling exist on the surface. The degree of undulations such as unavoidable rolling textures may depend on the finishing rollers used in the final step of rolling.
[0060] (2) Regarding oxide layer 2
[0061] The oxide layer 2 provided on the surface of the cathode substrate 1 may be an anodic oxide film or a natural oxide film. In addition, when the oxide layer 2 is an anodic oxide film, it may be a barrier film or a porous film. As a formation method, a known anodic oxidation method may be used, for example, a chemical conversion treatment using a chemical conversion solution such as an aqueous ammonium borate solution, an aqueous ammonium adipate solution, and an aqueous ammonium phosphate solution may be used.
[0062] (3) Inorganic conductive layer 3
[0063] Whether to provide an inorganic conductive layer 3 between the oxide layer 2 and the organic conductive layer 6 can be arbitrarily selected according to the structure of the capacitor to be finally obtained. For example, in existing solid electrolytic capacitors, a cathode collector having an inorganic conductive layer 3 as the outermost layer is often used. On the other hand, in existing hybrid electrolytic capacitors, a cathode collector having an oxide layer (including an oxide of a valve metal constituting a cathode substrate) as the outermost layer and a cathode collector having an inorganic conductive layer as the outermost layer are used. Therefore, in the cathode collector of the present invention, it is also possible to arbitrarily select whether to provide an inorganic conductive layer.
[0064] It should be noted that the dense layer 4 in the present invention has high adhesion not only to the oxide layer 2, but also to the inorganic conductive layer 3. Therefore, by providing the dense layer 4, whether or not the inorganic conductive layer 3 is present, the adhesion between the layer on the cathode substrate 1 side (the oxide layer 2 when the inorganic conductive layer 3 is not provided, and the inorganic conductive layer 3 when the inorganic conductive layer 3 is provided. The same applies hereinafter) and the organic conductive layer 6 can be improved, and the effect of the present invention can be obtained.
[0065] The inorganic conductive layer 3 may be a single layer, or may be formed of two or more layers using different inorganic conductive materials.
[0066] There is no particular limitation on the type of inorganic conductive material forming the inorganic conductive layer 3 and the method for forming the inorganic conductive layer 3, as long as sufficient adhesion to the oxide layer in the cathode can be ensured, or the particles of the inorganic conductive material can penetrate the oxide layer and firmly adhere to the cathode substrate 1.
[0067] As the inorganic conductive material, for example, carbon, titanium, aluminum, tantalum, chromium, niobium, vanadium, tungsten, hafnium, copper, platinum, gold, silver, cobalt, nickel, and iron can be used. In addition, as the formation method, vacuum evaporation, sputtering, ion plating, CVD (chemical vapor deposition), ALD (atomic layer deposition), coating, electrolytic plating, and electroless plating can be used.
[0068] (4) Organic conductive layer
[0069] (4-1) Organic Conductive Layer 6
[0070] The organic conductive layer 6 in the cathode current collectors 7 and 8 is formed by a dense layer 4 provided on the surface of the layer on the cathode substrate 1 side, and a porous layer 5 provided on the surface of the dense layer 4 and in contact with the solid electrolyte layer. It should be noted that the porous layer 5 may have a multilayer structure formed by a plurality of porous layers having different porosities in adjacent layers.
[0071] Regarding the cathode substrate 1 side, in order to reduce the contact resistance between the layer on the cathode substrate 1 side and the organic conductive layer 6, it is preferred to increase the contact points between the layer on the cathode substrate 1 side and the organic conductive layer 6. Since there are technical problems in the adhesion between the solid electrolyte layer and the cathode substrate 1, it is necessary to set it so that there is no contact point between the solid electrolyte layer and the cathode substrate 1. Therefore, in order to reduce the space between the layer on the cathode substrate 1 side and the organic conductive layer 6 where the solid electrolyte enters, a dense organic conductive layer (dense layer 4) is formed on the surface of the layer on the cathode substrate 1 side.
[0072] Although it is related to the organic conductive layer 11 in the electrolytic capacitor described below, it should be noted that in the hybrid electrolytic capacitor, the electrolyte is impregnated to make the element. The electrolyte impregnation is performed after the solid electrolyte layer is formed. That is, in the step of forming the solid electrolyte layer, the dispersion of the conductive polymer is first allowed to enter the porous layer 5, and then the surface of the dense layer 4 formed under the porous layer 5 is closely fitted by vacuum impregnation, so that the pores are reduced and become dense, and become integrated with the solid electrolyte layer. Before the solid electrolyte layer is formed, the organic conductive layer 6 composed of the dense layer 4 and the porous layer 5 becomes an organic conductive layer 11 composed of the dense layer 4 and the porous layer 5 with reduced pores and more dense.
[0073] For the solid electrolyte layer side, in order to improve the adhesion between the organic conductive layer 6 and the solid electrolyte layer by the anchoring effect and reduce the resistance between the organic conductive layer 6 and the solid electrolyte layer, it is preferred to increase the contact area between the organic conductive layer 6 and the solid electrolyte layer. Therefore, in the cathode current collectors 7 and 8 of one embodiment of the first aspect of the present invention, a porous organic conductive layer (porous layer 5) is formed on the surface of the dense layer 4 as a layer in contact with the solid electrolyte layer.
[0074] It should be noted that, for example, in Patent Document 2, although the adhesion is improved by providing a dense organic conductive layer, the electrolyte will penetrate into the interface between the cathode collector and the solid electrolyte layer, and the problem of poor contact still exists. However, since the solid electrolyte layer is kept with the electrolyte by impregnation with the electrolyte, although there is a possibility that the electrolyte penetrates into the interface between the organic conductive layer and the solid electrolyte layer and the contact becomes poor, in the cathode collectors 7 and 8 of the present invention, the outermost layer is not smooth but porous, so the poor contact can be suppressed by the anchoring effect.
[0075] The organic conductive layer 6 is preferably an electrolytic polymerized film in order to be formed with good adhesion on the surface of the layer on the cathode substrate 1 side.
[0076] In the case of the cathode current collector 7 which does not contain the inorganic conductive layer 3, an electropolymerized film is formed on the surface of the oxide layer 2. Therefore, an object having a power supply layer pre-set on the surface of the oxide layer 2 is used as a working electrode for electropolymerization. Here, the power supply layer can be formed using a known method. For example, a very thin conductive polymer dispersion is pre-coated on the surface of the oxide layer 2. In addition, the pre-coated power supply layer can be an inorganic conductive material (for example, manganese dioxide). Furthermore, the pre-coated power supply layer can also be an organic conductive material. In the case of an organic conductive material, it becomes a part of the organic conductive layer 6 through subsequent electropolymerization.
[0077] On the other hand, in the case of cathode current collector 8, inorganic conductive layer 3 is already formed on the surface of oxide layer 2. Therefore, the cathode substrate 1 having oxide layer 2 and inorganic conductive layer 3 formed thereon in this order can be used as a working electrode for electrolytic polymerization.
[0078] In a polymerization solution containing at least monomers, supporting electrolytes and solvents, a cathode substrate 1 having a pre-coating layer or an inorganic conductive layer 3 formed on the surface of the oxide layer 2 and a counter electrode formed of platinum or the like are immersed, and a voltage is applied between the pre-coating layer and the counter electrode or between the inorganic conductive layer 3 and the counter electrode, and an electrolytic polymerization film is formed by such constant current polymerization or constant potential polymerization. There is no particular limitation on the solvent used for electrolytic polymerization, and a solution that can dissolve the required amount of monomers and supporting electrolytes and has no negative impact on the electrolytic polymerization can be used, and an aqueous solvent can be selected. It should be noted that, according to the electrolytic conditions of the electrolytic polymerization, the dense layer 4 and the porous layer 5 can be produced separately.
[0079] There is no particular limitation on the type of the conductive polymer included in the organic conductive layer 6, and a known conductive polymer derived from a monomer having a π-conjugated double bond can be used. Among them, thiophene or its derivatives can be preferably used based on the fact that high conductivity and high-temperature durability can be obtained. As derivatives of thiophene, for example, 3,4-ethylenedioxythiophene, 3-alkylthiophene, 3-alkoxythiophene, 3-alkyl-4-alkoxythiophene, 3,4-alkylthiophene, 3,4-alkoxythiophene, and alkylated ethylenedioxythiophene in which the above-mentioned 3,4-ethylenedioxythiophene is modified with an alkyl group can be listed. In addition, as a supporting electrolyte that becomes a dopant, a sulfonated polyester can be used. Sulfonated polyester is a polymer anion that enters the polymer of thiophene or its derivative obtained by electrolytic polymerization and functions as a dopant.
[0080] (4-1-a) About dense layer 4
[0081] The dense layer 4 in the organic conductive layer 6 exists at the interface between the organic conductive layer 6 and the oxide layer 2 in the cathode current collector 7, or exists at the interface between the organic conductive layer 6 and the inorganic conductive layer 3 in the cathode current collector 8. Here, "existing at the interface" means that a layer structure that exists continuously between the organic conductive layer 6 and the oxide layer 2 in the cathode current collector 7 or between the organic conductive layer 6 and the inorganic conductive layer 3 in the cathode current collector 8 is formed.
[0082] In addition, the dense layer 4 refers to a layer in which the substances forming the organic conductive layer are continuously bonded in a manner that there is no space for other substances to enter the interior of the layer, and there is almost no pore state. Furthermore, "almost no pore state" means that in cross-sectional observation using a scanning electron microscope, when observing at a magnification of 50,000 times, the number of pores with a maximum diameter of 20 nm or more that can be seen with the naked eye for all 10 fields of view observed is less than 5 per 1 μm thickness.
[0083] It should be noted that even if it is assumed that there are partially discontinuous positions due to the presence of pores, if the pores are not continuously connected between the oxide layer 2 and the porous layer 5 in the cathode collector 7 or between the inorganic conductive layer 3 and the porous layer 5 in the cathode collector 8, and there is not even one pore with a diameter greater than the thickness of the dense layer 4 between the oxide layer 2 and the porous layer 5 in the cathode collector 7 or between the inorganic conductive layer 3 and the porous layer 5 in the cathode collector 8, then this situation is also included in the “continuously existing layer structure”.
[0084] In the case where the surface of the cathode substrate 1 is subjected to a roughening treatment such as etching in advance, the organic conductive layer 6 grows in a manner that blocks the surface portion of the concave portion formed by the roughening treatment. If it reaches a position on the surface where no concave portion is formed, it grows uniformly on the surface, just as when the surface of the cathode substrate 1 is smooth. In addition, at this time, by adjusting the electrolytic conditions of the electrolytic polymerization, the organic conductive layer that grows uniformly on the surface can be in a state with almost no pores. Therefore, even if the cathode substrate 1 is subjected to a roughening treatment in advance, the dispersion liquid and the electrolyte containing the conductive polymer dispersion that becomes the solid electrolyte will be blocked by the dense layer 4 and will not penetrate into the concave portion extending from the surface of the cathode substrate 1 to the inside formed by the roughening treatment.
[0085] In the cathode current collectors 7 and 8 of one embodiment of the first aspect of the present invention, the thickness of the dense layer 4 is not particularly limited. In order to more reliably ensure the contact with the layer on the cathode substrate 1 side so as to fully suppress the penetration of the dispersion of the conductive polymer that serves as the solid electrolyte, the thickness of the dense layer 4 is preferably above a certain value, preferably above 0.02 μm.
[0086] However, when the thickness is too thick, the organic conductive layer 6 may peel off due to stress under the long-term heat load of use due to the difference in thermal expansion coefficients between the cathode substrate 1 and the organic conductive layer 6, resulting in an increase in ESR. Therefore, the thickness of the dense layer 4 is preferably less than a certain thickness, preferably less than 15 μm.
[0087] It should be noted that the oxide layer 2 used for the cathode current collector of the electrolytic capacitor is usually 0.1 μm or less, and the thickness of the inorganic conductive layer 3 is usually 3 μm or less on average, which is thin enough not to be a major cause of peeling caused by the difference in thermal expansion coefficient.
[0088] Therefore, based on the ability to fully and more reliably suppress the penetration of the conductive polymer dispersion into the layer on the cathode substrate 1 side and the organic conductive layer 6, and to more reliably suppress the peeling of the organic conductive layer 6 caused by the long-term heat load accompanying use, the thickness of the dense layer 4 is preferably greater than 0.02 μm and less than 15 μm.
[0089] The dense layer 4 is preferably an electrolytic polymerized membrane. The formation of the dense layer 4 and the porous layer 5 is determined by the polymerization conditions.
[0090] Specifically, it is determined by the growth rate (polymerization rate) representing electrochemical charge transfer, and a dense layer 4 is formed when the monomer concentration (the water and organic solvent ratio needs to be adjusted together) is low, the diffusion of the monomer is rate-limiting, and the polymerization rate is slow.
[0091] On the other hand, when the monomer concentration (the ratio of water to the organic solvent needs to be adjusted together) is sufficient and there is no problem with the diffusion of the monomer, the fibrous polymer will have a folded structure by increasing the polymerization rate, thereby forming the porous layer 5 .
[0092] The dense layer 4 grows in a manner that covers the surface of the conductive substrate. However, the slower the polymerization rate, the longer the manufacturing process and the higher the cost, so the thickness of the dense layer 4 is more preferably greater than 20 nm and less than 2.5 μm. It should be noted that during the electrolytic polymerization process, the ions released from the supporting electrolyte are contained in the organic conductive layer of the conductive polymer as dopants.
[0093] (4-1-b) Regarding the porous layer 5
[0094] The porous layer 5 refers to a material that can form an organic conductive layer, a layer formed in such a way that the layer has spaces (pores) inside which other materials can enter, and a layer in which a plurality of pores can be seen with the naked eye in the thickness direction when the cross-section is observed at a magnification of 50,000 times under a scanning electron microscope. Figure 5 Such a cross section has a structure having pores inside that extend to the outer surface of the cathode current collector.
[0095] The thickness of the porous layer 5 is not particularly limited. If it is too thin, sufficient anchoring effect and sufficient adhesion may not be obtained. When the thickness of the porous layer 5 is less than 2 μm, there is a tendency that the anchoring effect and adhesion are insufficient. Therefore, the thickness of the porous layer 5 is preferably 2 μm or more.
[0096] However, when the porous layer 5 is too thick, the size of the capacitor element will increase, the distance between the cathode substrate 1 and the anode substrate will increase, and the ESR will increase. In addition, the residue of the electrolyte used for electrolytic polymerization will increase the ESR change rate. Therefore, when the thickness of the porous layer 5 is greater than 25 μm, it is difficult to completely remove the residue in the pores of the porous layer 5 even if it is cleaned, and the ESR change rate will increase. Therefore, the thickness of the porous layer 5 is preferably less than 25 μm.
[0097] Therefore, based on the viewpoint that sufficient adhesion with the solid electrolyte layer can be more reliably obtained by obtaining a sufficient anchoring effect with the solid electrolyte layer, and that the increase in the ESR change rate caused by the electrolyte residue in the pores of the porous layer 5 can be more reliably suppressed, the thickness of the porous layer 5 is preferably greater than 2 μm and less than 25 μm.
[0098] Furthermore, although the conductive polymer will enter the porous layer when impregnated to form a solid electrolyte, the anchoring effect will not change even if the thickness is greater than 12 μm. In addition, the thicker the porous layer 5 is, the longer the washing step for removing the residue of the electrolyte has to be. Based on the above, based on more reliably ensuring sufficient adhesion with the solid electrolyte layer, and more reliably suppressing the increase in the ESR change rate caused by the residue of the electrolyte, and being able to shorten the cleaning step for removing the residue of the electrolyte, that is, shortening the manufacturing steps of the cathode collectors 7 and 8, the thickness of the porous layer 5 is more preferably 2 μm or more and 12 μm or less.
[0099] The porosity of the porous layer 5 is not particularly limited, but if the porosity is too small, the contact area with the solid electrolyte layer becomes too small to obtain a sufficient anchoring effect, and sufficient adhesion cannot be obtained. In addition, when the cathode current collector 7 or 8 with a small porosity of the porous layer 5 is used in the electrolytic capacitor of the present invention, it is difficult to achieve further high durability. In addition, if the porosity is too large, it is easy to peel off from the dense layer 4, and there will be problems with adhesion such as peeling when the element is curled.
[0100] Therefore, based on the viewpoints of obtaining sufficient anchoring effect with the solid electrolyte layer, obtaining sufficient adhesion with the solid electrolyte layer to achieve further high durability, and being able to suppress peeling from the dense layer 4, the porosity of the porous layer 5 is preferably 0.1 or more and 0.7 or less. In addition, based on the viewpoints of being able to suppress peeling from the dense layer 4 and further improving the anchoring effect with the solid electrolyte layer, the porosity of the porous layer 5 is more preferably 0.3 or more and 0.7 or less.
[0101] Here, the anchoring effect of the porous layer 5 on the solid electrolyte layer is described. In the step of forming the solid electrolyte layer of the electrolytic capacitor, a dispersion containing a conductive polymer to become the solid electrolyte layer is vacuum impregnated, and then dried and solidified by heat treatment. And during solidification, since the outermost layer of the cathode current collectors 7 and 8 is the porous layer 5, the solid electrolyte is wrapped in the pores of the porous layer 5 while shrinking, and the solid electrolyte layer is more firmly adhered to.
[0102] The porous layer 5 is preferably an electrolytic polymerization membrane. In the case of electrolytic polymerization, when the monomer concentration (the ratio of water to organic solvent needs to be adjusted at the same time) is sufficient and there is no problem with the diffusion of the monomer, by accelerating the polymerization rate, a structure with larger pores such as an aggregate of a fiber structure can be obtained. In addition, the porosity of the porous layer 5 can be controlled by controlling the drying conditions after the organic conductive layer with such a structure with larger pores is formed. The higher the drying temperature, the lower the porosity, that is, the lower the porosity, and the lower the drying temperature, the higher the porosity, that is, the higher the porosity. In addition, the higher the drying temperature, the lower the porosity and the higher the density of the porous layer 5, as a result of which the thickness of the porous layer 5 becomes thinner.
[0103] The porous layer 5 may be a multilayer structure in which the porosity of adjacent layers is different from each other. The porosity of each layer constituting the porous layer 5 may be gradually increased or gradually decreased from the side formed on the surface of the dense layer 4. In addition, the high and low porosities may be interchangeable. In addition, the porosity of a part of the layers constituting the porous layer 5 and the adjacent layers may be the same, or the porosity of all the layers constituting the porous layer 5 may be the same. That is, how to set the porosity of each layer constituting the porous layer 5 is arbitrary.
[0104] In the case where the porous layer 5 has a multilayer structure, there is no particular upper limit on the number of layers constituting the porous layer 5 .
[0105] In order to make the porous layer 5 a multilayer structure in which the porosity of adjacent layers is different from each other, the porous layer 5 can be formed by a method of controlling the drying conditions in multiple stages, or by a manufacturing step of multiple stages with intermediate drying. For example, in order to increase the porosity of the porous structure from the cathode substrate 1 side toward the outer layer in order to improve the adhesion with the solid electrolyte layer without deteriorating the adhesion with the cathode substrate 1 side, electrolytic polymerization and subsequent drying can be repeated, and the drying temperature can be lowered in turn for each repetition in the process.
[0106] (4-2) Organic Conductive Layer 9
[0107] The organic conductive layer 9 of the cathode current collector 10 according to one embodiment of the second aspect of the present invention is formed of a dense layer provided on the surface of the layer on the cathode substrate 1 side.
[0108] Regarding the cathode substrate 1 side, in order to suppress the penetration of the conductive polymer dispersion toward the layer on the cathode substrate 1 side and the organic conductive layer 9 when the conductive polymer serving as the solid electrolyte is impregnated, a dense layer is formed on the surface of the layer on the cathode substrate 1 side. In addition, in order to sufficiently suppress the penetration of the electrolyte when the electrolyte is impregnated, the thickness of the organic conductive layer 9 is greater than 2 μm. Furthermore, in order to sufficiently reduce the influence of the deterioration of the adhesion over time caused by the penetration of the electrolyte, the thickness of the organic conductive layer 9 is preferably greater than 2.5 μm.
[0109] However, when the organic conductive layer 9 is too thick, the size of the capacitor element becomes larger, the distance between the cathode substrate 1 and the anode substrate becomes longer, and the ESR increases, so the thickness of the organic conductive layer 9 is set to 22 μm or less. In addition, when it is too thick, due to the difference in thermal expansion coefficients between the cathode substrate and the organic conductive layer, the peeling of the organic conductive layer 9 caused by stress under the action of long-term heat load accompanying use becomes a problem, resulting in a problem of increased ESR. Therefore, the thickness of the organic conductive layer 9 is preferably 15 μm or less.
[0110] Therefore, in order to fully suppress the penetration of the conductive polymer dispersion and the electrolyte, and to suppress the increase in ESR caused by the distance between the cathode substrate 1 and the anode substrate, the organic conductive layer 9 is selected to be composed of a dense layer provided on the surface of the layer on the cathode substrate 1 side, and the thickness of the organic conductive layer 9 is greater than 2μm and less than 22μm. In addition, based on the viewpoint of sufficiently reducing the influence of the deterioration of the adhesion due to the penetration of the electrolyte and suppressing the peeling of the organic conductive layer 6 caused by the long-term heat load accompanying use, the thickness is preferably 2.5μm or more and 15μm or less.
[0111] It should be noted that the definition of the dense layer in the organic conductive layer 9 is the same as that of the dense layer 4 in the organic conductive layer 6. In addition, the method for manufacturing the dense layer in the organic conductive layer 9 is also the same as that of the dense layer 4 in the organic conductive layer 6. In addition, the method for evaluating the dense layer in the organic conductive layer 9 is also the same as that of the dense layer 4 in the organic conductive layer 6.
[0112] 2. About electrolytic capacitors
[0113] The electrolytic capacitors of the third and fourth aspects of the present invention use at least a solid electrolyte containing a conductive polymer as an electrolyte component and are solid electrolytic capacitors or hybrid electrolytic capacitors. It should be noted that only the organic conductive layer is described here with respect to the cathode current collector.
[0114] (1) About anode
[0115] There is no particular limitation, and the anode used in the existing electrolytic capacitor can be used. For example, an anode substrate formed of a valve metal is subjected to a surface enlargement treatment, and then an anodization treatment is performed to form a dielectric oxide film on the surface of the anode substrate after the surface enlargement treatment.
[0116] As the material of the anode substrate, for example, aluminum, tantalum, niobium and titanium can be used. In addition, the anode substrate can be in the form of a foil or a wire, for example. Moreover, the anode substrate is preferably an aluminum foil.
[0117] As a method of surface expansion treatment, for example, etching, vapor deposition and sintering can be used. Here, when etching is selected as the surface expansion treatment, it can be chemical etching or electrochemical etching. In addition, the holes formed by etching can be sponge-like holes, tunnel-like holes, or a combination of the two. In addition, when vapor deposition or sintering is selected as the surface expansion treatment, the material of the particles formed by the valve metal deposited on the surface of the anode substrate can be the same as or different from the material of the anode substrate.
[0118] As the electrolyte used in the anodizing treatment, for example, an aqueous ammonium adipate solution, an aqueous ammonium phosphate solution, and an aqueous ammonium borate solution can be used.
[0119] (2) Solid electrolyte layer
[0120] The type of the conductive polymer in the solid electrolyte layer is not particularly limited, and conductive polymers derived from monomers having π-conjugated double bonds used in existing electrolytic capacitors can be used. In addition, it can be derived from the same monomer as the conductive polymer contained in the organic conductive layer 6 or 9, or it can be derived from a different monomer. Among them, from the viewpoint of obtaining particularly high conductivity and high-temperature durability, it is more preferred that not only the conductive polymer contained in the organic conductive layer 6 or 9, but also the conductive polymer in the solid electrolyte layer is poly(3,4-ethylenedioxythiophene).
[0121] At present, in an electrolytic capacitor including a cathode collector using a cathode substrate formed of a valve metal, the solid electrolyte layer used in the electrolytic capacitor includes two types: a layer formed using a dispersion liquid containing a dispersion formed of particles of a conductive polymer and a dispersion medium, and a layer formed using chemical polymerization using a monomer and an oxidant. The present invention, as described so far, has exerted a significant effect, especially in the case of using a solid electrolyte layer using a dispersion liquid, and can also exert an effect when using chemical polymerization. That is, in chemical polymerization, the surface of the cathode collector becomes acidic and damaged during the chemical polymerization of the monomer and the oxidant, which becomes a problem. Therefore, by forming an organic conductive layer that hinders the penetration of the polymerization liquid of the monomer and the oxidant on the surface of the cathode collector, it is possible to reduce the damage to the surface of the cathode collector during chemical polymerization, and it is possible to achieve low ESR and high durability.
[0122] (3) Regarding electrolyte
[0123] An electrolyte used in an existing electrolytic capacitor that includes at least a solvent and a solute dissolved therein can be used, and can be appropriately selected according to the requirements such as the operating temperature required by the hybrid electrolytic capacitor. As an electrolyte, for example, an electrolyte in which a solute such as benzoate, phthalate, terephthalate, salicylate, tartrate, oxalate, glutarate, adipate, azelaate, maleate, fumarate and citrate is dissolved in a solvent such as γ-butyrolactone, ethylene glycol, diethylene glycol, ethylene glycol monomethyl ether, cyclopentane, 3-methylcyclopentane, 2,4-dimethylcyclopentane, acetonitrile, water, etc. can be used. As salts, quaternary ammonium salts such as ammonium salts, tetramethylammonium salts and triethylmethylammonium salts, quaternized ammonium salts such as ethyldimethylimidazolinium salts and tetramethylimidazolinium salts, and amine salts such as trimethylamine salts and triethylamine salts can be exemplified. The above-mentioned solvent can be used alone or in combination of two or more thereof. The above-mentioned solute can be used alone or in combination of two or more thereof. These electrolytes may contain known additives in addition to the above-mentioned solvent and solute.
[0124] (4) About diaphragm
[0125] There is no particular limitation, and a separator used in a conventional electrolytic capacitor can be used. For example, a woven or nonwoven fabric or mixed paper made of cellulose fiber, a resin derived therefrom, or the like can be used.
[0126] (5) About capacitors
[0127] Terminals are connected to the anode and cathode collectors 7, 8 or 10 obtained above, respectively, so that the dielectric layer of the anode is opposite to the organic conductive layer 6 of the cathode collector 7 or 8, or to the organic conductive layer 9 of the cathode collector 10, through the diaphragm, to form a capacitor element. It should be noted that the capacitor element can be a rolled type or a stacked type. In addition, there is no particular limitation on either the anode terminal or the cathode terminal, and the terminal used in the existing electrolytic capacitor can be used.
[0128] Next, after the capacitor element is repaired and chemically converted, the capacitor element is dried. Thereafter, the capacitor element is impregnated with a dispersion liquid containing a dispersion formed of particles of a conductive polymer and dried repeatedly to form a solid electrolyte. Thereafter, the obtained capacitor element is sealed in an outer casing to obtain a solid electrolytic capacitor.
[0129] Here, in the case of obtaining a hybrid electrolytic capacitor, the process is performed until the solid electrolyte layer is formed, similarly to the case of obtaining a solid electrolytic capacitor, and then the obtained element is impregnated with an electrolyte solution and then sealed in an outer case.
[0130] (6) Organic conductive layer 11 in electrolytic capacitor
[0131] The organic conductive layer 11 in the electrolytic capacitor is closely attached to the surface of the oxide layer 2, and the thickness of the organic conductive layer 11 is set to be greater than 2 μm and less than 22 μm. It should be noted that when the inorganic conductive layer 3 is formed on the surface of the oxide layer 2, the organic conductive layer 11 is closely attached to the surface of the inorganic conductive layer 3. As a result, the number of contact points between the layer on the cathode substrate 1 side and the organic conductive layer 11 increases, which can reduce the resistance between the layer on the cathode substrate 1 side and the organic conductive layer 11. In addition, the penetration of the dispersion liquid containing the conductive polymer dispersion and the penetration of the electrolyte can be fully suppressed. The method for confirming whether the organic conductive layer 11 is closely attached to the layer on the cathode substrate 1 side is described in detail below.
[0132] The structure of the cathode current collector 12 in the electrolytic capacitor of the present invention is Figure 4. As described above, in the process of assembling the cathode current collector into the capacitor element, the steps of impregnating the capacitor element with a dispersion of a conductive polymer that becomes a solid electrolyte layer and performing a heat treatment are included. The impregnation mainly uses a vacuum impregnation method. During this process, when the organic conductive layer before forming the solid electrolyte layer includes a porous layer 5, the porous layer 5 is compressed and closely adheres to the surface of any one of the dense layer 4, the inorganic conductive layer 3 or the oxide layer 2 formed under the porous layer 5, and the pores are reduced and become more dense (it should be noted that when the porous layer 5 has a multilayer structure in which the porosity of multiple adjacent layers is different from each other, all the layers constituting the porous layer 5 are compressed, and the pores are reduced and become more dense). Therefore, it goes without saying that the organic conductive layer before forming the solid electrolyte layer is composed only of the dense layer 4. Even in the case where it is composed of the dense layer 4 and the porous layer 5 formed on the surface of the dense layer 4 and in the case where it is composed only of the porous layer 5, the organic conductive layer 11 is also as Figure 4 As shown in the schematic diagram of , the surface of the layer provided on the cathode substrate 1 side is in close contact.
[0133] It should be noted that, in the organic conductive layer 11 , the dense layer 4 and the porous layer 5 before being incorporated into the capacitor element are difficult to be individually distinguished.
[0134] As described above, after the solid electrolyte layer is formed, it is impregnated with an electrolyte. At this time, the electrolyte is easier to penetrate than the dispersion of the conductive polymer that becomes the solid electrolyte. In order to fully suppress the electrolyte from penetrating between the layer on the cathode substrate 1 side and the organic conductive layer 11, the organic conductive layer 11 needs to be thicker than a certain thickness. However, when it is too thick, the size of the capacitor element will become larger, the distance between the cathode substrate 1 and the anode substrate will become longer, and the ESR will increase. Therefore, in order to fully suppress the penetration of the electrolyte and suppress the increase in ESR caused by the distance between the cathode substrate 1 and the anode substrate, the thickness of the organic conductive layer 11 is greater than 2μm and less than 22μm.
[0135] In addition, when it is too thin, the influence of poor adhesion caused by the penetration of the electrolyte over time cannot be fully reduced. When it is too thick, since the thermal expansion coefficients of the cathode substrate 1 and the organic conductive layer 11 are different, the peeling of the organic conductive layer 11 caused by stress under the action of the long-term heat load accompanying use becomes a problem, and as a result, the ESR increases. Therefore, with respect to the penetration of the electrolyte, based on the viewpoint that even the penetration over time can be suppressed and the influence of poor adhesion can be reduced, and based on the viewpoint that in addition to the increase in ESR caused by the distance between the cathode substrate 1 and the anode substrate, the increase in ESR caused by the long-term heat load accompanying use can also be suppressed, the thickness of the organic conductive layer 11 is preferably 2.5 μm or more and 15 μm or less.
[0136] It should be noted that the cathode current collector taken out by decomposing the capacitor is obtained in a state where a solid electrolyte layer is tightly attached to the surface. Next, the solid electrolyte layer is removed as much as possible by washing. Since the solid electrolyte layer has weaker adhesion than the organic conductive layer, only the solid electrolyte layer can be removed except for the solid electrolyte layer that enters the organic conductive layer 11. Washing can be performed using water or an organic solvent to remove it. Afterwards, the thickness can be measured using the same method as the organic conductive layer of the cathode current collector before it becomes a capacitor. It should be noted that the solid electrolyte layer that enters the organic conductive layer 11 can be treated as a part of the organic conductive layer 11.
[0137] It should be noted that in order to obtain the electrolytic capacitor provided by the fourth aspect of the present invention, when the dense layer 4 in the cathode collector before being assembled into the capacitor element is less than 2μm, it is necessary to further form a porous layer 5. The thinner the dense layer 4, the thicker the porous layer 5 is formed.
[0138] 3. About the evaluation method
[0139] (1) Whether a dense layer 4 is formed
[0140] A cross-sectional polisher was used to prepare a cross-sectional sample of a cathode collector before being assembled into a capacitor element, in which an organic conductive layer was formed. A scanning electron microscope was used to observe 10 fields of view at a magnification of 50,000 times by changing the observation position. Then, in each field of view, the number of pores that can be observed in the image is confirmed for the layer set on the surface of the layer on the cathode substrate 1 side. At this time, in all of the 10 fields of view observed, if the number of pores with a maximum diameter of 20 nm or more that can be observed through the image satisfies the frequency of less than 5 per 1 μm thickness, it is judged that a dense layer 4 is formed on the cathode substrate 1 side. Here, "the number of pores satisfies the frequency of less than 5 per 1 μm thickness" means that when the number of pores is confirmed while scrolling the range of 1 μm thickness from the interface of the layer on the cathode substrate 1 side and the organic conductive layer toward the outer surface of the cathode collector, the number of pores existing in the range of 1 μm thickness is less than 5. The dense layer is considered to be the layer before the top pores at a frequency of 5 or more per 1 μm thickness. In addition, when there are 5 or more pores within a range of 1 μm from the interface between the layer on the cathode substrate 1 side and the organic conductive layer, the thickness toward the cathode substrate 1 side is successively subtracted by 1 μm until the number of pores is less than 5, and the layer before the top pores at a frequency of 5 or more is considered to be the dense layer.
[0141] It should be noted that when the thickness of the layer set on the surface of the layer on the cathode substrate 1 side is greater than the thickness that can be accommodated in one field of view at a magnification of 50,000 times, by sequentially changing the observation position in the film thickness direction, it is possible to confirm the number of pores in all parts in the film thickness direction.
[0142] (2) Thickness of the dense layer 4
[0143] For the layer set on the cathode substrate 1 side, after confirming that it is a dense layer 4, change the observation position and measure its thickness in 10 fields of view using the length measurement function of a scanning electron microscope. Specifically, the number of pores is confirmed along the film thickness direction starting from the interface between the layer on the cathode substrate 1 side, and the thickness is measured until the number of pores with a maximum diameter of more than 20nm satisfies the frequency of more than 5 per 1μm thickness and is located in front of the top pore. The observation magnification when measuring the thickness is selected to be the maximum magnification in the film thickness direction that can accommodate the dense layer 4 set on the cathode substrate 1 side in one field of view. Then, the thickness in each field of view is averaged and regarded as the thickness of the dense layer 4. It should be noted that the observation positions of the 10 fields of view when measuring the thickness and the 10 fields of view when confirming whether a dense layer has been formed can be different or the same.
[0144] (3) Regarding the presence or absence of porous layer 5
[0145] For the layer provided on the surface of the layer on the cathode substrate 1 side, when it is confirmed that it is a dense layer 4 and its thickness is measured, for the organic conductive layer provided on the surface of the dense layer 4, the number of pores observable through the image is confirmed for 10 fields of view with the observation position changed in the same manner as (1). At this time, when the number of pores with a maximum diameter of 20 nm or more that can be observed through the image in all of the 10 fields of view observed satisfies a frequency of 5 or more per 1 μm thickness, it is determined that a porous layer 5 is formed. It should be noted that in determining whether there is a porous layer, when the number of pores is confirmed in sequence along the film thickness direction starting from the boundary with the dense layer 4, the number of pores contained in a thickness of 1 μm is used.
[0146] (4) Thickness of the porous layer 5
[0147] For the layer provided on the surface of the dense layer 4, after confirming that it is the porous layer 5, the observation position is changed and the thickness from the interface between the dense layer 4 and the porous layer 5 to the outer surface of the porous layer 5 is measured in 10 fields of view using the length measurement function of the scanning electron microscope. It should be noted that the observation magnification when measuring the thickness is the maximum magnification that can accommodate the porous layer 5 provided on the surface of the dense layer 4 in one field of view in the film thickness direction. Then, the average value of the thickness of the layer confirmed as the porous layer 5 in each field of view is taken as the thickness of the porous layer 5.
[0148] (5) Porosity of the porous layer 5
[0149] Here, the porosity of the porous layer 5 is calculated using the film thickness a of the porous layer 5 and the film thickness c of the organic conductive layer after the pores are compressed and densified (hereinafter referred to as the "compressed densified layer"). First, the organic conductive layer 6 is compressed and dried while being wet, so that the pores of the porous layer 5 are compressed and the porous layer 5 becomes a compressed densified layer. Therefore, the change in film thickness before and after compression and densification indicates the degree of porosity. Therefore, the wetted cathode collector 7 or 8 is sandwiched between the diaphragm and the glass plate, and dried under pressure at a temperature of more than 100°C and less than 150°C, and a compressed densified layer is formed by the organic conductive layer 6 composed of the porous layer 5 and the dense layer 4. The thickness c (cm) of the compressed and densified layer thus formed is calculated in the same manner as (4). The value obtained by adding the thickness a of the porous layer calculated by (4) and the thickness b of the dense layer calculated by (2) minus c is divided by the film thickness a of the porous layer before compression and densification and is defined as the porosity d (Formula 1).
[0150] d=(a+b-c) / a··· (Formula 1)
[0151] It should be noted that when the porous layer 5 has a multilayer structure in which adjacent layers have different porosities, the overall porosity of each layer is calculated using the above-mentioned formula 1. The overall porosity can be regarded as the porosity of the porous layer 5.
[0152] In order to confirm whether the porous layer 5 has a multilayer structure in which the porosity of adjacent layers is different from each other, the ratio of the pore portion obtained by binarizing the image can be used. Specifically, the maximum magnification that can accommodate all the layers set on the surface of the cathode substrate 1 in one field of view in the film thickness direction of the porous layer 5 is observed, and the observed image is binarized to find the ratio of the pore portion of each layer constituting the porous layer 5. In addition, when there is a layer whose ratio is different from that of the adjacent layer by more than 15%, it can be judged that the porous layer 5 has a multilayer structure in which the porosity of adjacent layers is different from each other. It should be noted that the identification of the boundaries between the layers uses a scanning electron microscope to obtain a 10,000-fold image along the film thickness direction of the entire porous layer 5. Afterwards, each 1μm square image is binarized along the film thickness direction to find the ratio of the pore portion. Here, if there is a position where the ratio of the pore portion changes by more than 15%, the square of 1 μm is further subdivided along the film thickness direction and the ratio of the pore portion is calculated to determine the boundary position with a difference of more than 15%. The subdivision standard is 0.1 μm or more (less than 10 equal divisions). In addition, in the case where the film thickness is less than 1 μm, or for the part that cannot be completely accommodated by the unit of 1 μm, the evaluation after appropriate subdivision along the film thickness direction can also be used for judgment. It should be noted that instead of the porosity of formula 1, the porosity can be calculated from the ratio of the pore portion of each layer obtained in this way. In addition, the multilayer structure can be expressed by using both the value of the relative comparison of the ratio of the pore portion of each layer and the overall porosity.
[0153] (6) Confirmation of Adhesion of the Organic Conductive Layer 11 to the Cathode Substrate 1 in the Electrolytic Capacitor
[0154] The cathode collector 12 taken out by decomposing the capacitor element is washed with water or an organic solvent to remove the solid electrolyte, and then dried. After that, a cross-section polisher is used to prepare a cross-section sample of the cathode collector 12 formed with an organic conductive layer, and a scanning electron microscope is used to observe the interface between the cathode substrate side and the organic conductive layer in 10 fields of view at a magnification of 50,000 times by changing the observation position. In addition, the number of pores that exist in the interface and can be observed through the image is confirmed. At this time, for all of the 10 observed fields of view, when the number of pores with a maximum diameter of 20nm or more that can be observed by the naked eye meets the frequency of less than 5 per field of view, and when there are no pores in more than 90% of the interface, it is judged that the organic conductive layer 11 in the electrolytic capacitor is closely arranged on the cathode substrate 1 side.
[0155] (7) Thickness of the organic conductive layer 11 in the electrolytic capacitor
[0156] After confirming that the organic conductive layer provided on the cathode collector 12 taken out of the decomposed capacitor element is the organic conductive layer 11 closely provided on the cathode substrate 1 side, change the observation position and measure its thickness in 10 fields of view using the length measurement function of the scanning electron microscope. At this time, the thickness of the organic conductive layer 11 is measured in the portion where there is no residue of the solid electrolyte layer. The solid electrolyte layer that enters the organic conductive layer 11 is treated as a part of the organic conductive layer 11. The observation magnification is the maximum magnification that can accommodate the organic conductive layer 11 in one field of view in the film thickness direction. Then, the thickness in each field of view is averaged and regarded as the thickness of the organic conductive layer 11. It should be noted that the observation positions of the 10 fields of view when measuring the thickness and the 10 fields of view when confirming the close adhesion can be different or the same.
[0157] (8) ESR (load test)
[0158] Before the load test, the ESR (initial value) of the electrolytic capacitor was measured at 100kHz. Then, the rated voltage of the electrolytic capacitor was applied to the electrolytic capacitor in a constant temperature chamber at 125°C for 2000 hours. After that, the electrolytic capacitor was returned to room temperature and the ESR of the electrolytic capacitor was measured at 100kHz.
[0159] Example
[0160] The present invention is specifically described below based on the examples and comparative examples, but the present invention is not limited to the following examples. According to the following procedure, a rolled hybrid electrolytic capacitor having a cathode current collector as shown in Table 1 and a rated voltage of 35V was prepared and evaluated. In addition, a rolled solid electrolytic capacitor having a cathode current collector as shown in Table 2 and a rated voltage of 25V was prepared and evaluated.
[0161] <Example 1>
[0162] (1) Preparation of cathode current collector
[0163] A smooth aluminum foil is used as a cathode substrate for obtaining a cathode current collector. A natural oxide film exists on the surface of the cathode substrate. A carbon-containing inorganic conductive layer is formed on the natural oxide film by ion plating. 5 g of sulfonated polyester, 785 g of water, 197 g of acetonitrile, and 10 g of 3,4-ethylenedioxythiophene (EDOT) are mixed and stirred, and it is visually confirmed that there is no separation into two layers to prepare an electrolytic polymerization solution. Next, the aluminum foil (working electrode) on which the inorganic conductive layer is formed and the counter electrode of the SUS plate are immersed in the polymerization solution as the first stage at 0.1 mA / cm 2 After 2.5 minutes of constant current electropolymerization under the conditions of 0.5 mA / cm 2The constant current electrolytic polymerization was carried out for 14.3 minutes under the conditions of . After the working electrode after polymerization was washed with water, it was dried at 60°C for 30 minutes to obtain a cathode collector having an organic conductive layer formed on the inorganic conductive layer. It should be noted that the organic conductive layer in the cathode collector of Example 1 is a PEDOT (poly (3, 4-ethylenedioxythiophene)) layer having a dense layer of 0.2 μm thickness and a porous layer of 10.0 μm thickness and a porosity of 0.46.
[0164] (2) Anode preparation
[0165] An etched aluminum foil was used as an anode substrate for obtaining an anode. The aluminum foil was anodized using an aqueous ammonium adipate solution as a chemical conversion solution to form an anodic oxide film (dielectric layer) with a chemical conversion voltage of 56.0 V on the surface of the aluminum foil to obtain an anode.
[0166] (3) Preparation of capacitor elements
[0167] Terminals were connected to the obtained anode and cathode current collectors, and the dielectric layer of the anode and the organic conductive layer of the cathode current collector were stacked and rolled up with a separator interposed therebetween. 2 After the anode was repaired and chemically converted for 10 minutes under the conditions of , the capacitor element was dried at 30° C. for 6 hours.
[0168] (4) Formation of solid electrolyte layer
[0169] Microparticles (dispersion) of poly(3,4-ethylenedioxythiophene) doped with polystyrene sulfonic acid are dispersed in a dispersion medium in which 5% by mass of ethylene glycol is added to water to obtain a dispersion liquid for forming a solid electrolyte layer. The above-mentioned capacitor element is impregnated with the obtained dispersion liquid for 120 seconds under a reduced pressure atmosphere (90kPa), and then dried at 150°C for 20 minutes. The dispersion liquid impregnation and drying are repeated again to obtain a capacitor element with an added solid electrolyte layer. It should be noted that the organic conductive layer after the capacitor element is made is closely arranged on the inorganic conductive layer, and its thickness is 5.6μm.
[0170] (5) Fabrication of hybrid electrolytic capacitors
[0171] An electrolyte solution in which 5% by mass of ammonium borodisalicylate is dissolved in ethylene glycol is prepared. The electrolyte solution is quantitatively discharged into a capacitor element with a solid electrolyte layer added so that the solid electrolyte layer is impregnated with the electrolyte solution to obtain a capacitor element with a composite electrolyte layer. The obtained element is sealed in an outer casing. Next, a voltage of 35V is applied at 125°C for 45 minutes for aging treatment to obtain a hybrid electrolytic capacitor with a rated voltage of 35V.
[0172] (6) Evaluation of capacitor characteristics
[0173] As initial characteristics of the obtained capacitor, ESR at 100 kHz was measured at 20° C. Then, after being left at a high temperature of 125° C. for 2000 hours as a durability test, ESR at 100 kHz was measured again as characteristics after the durability test.
[0174] <Example 2>
[0175] An aluminum foil formed with sponge-like etching holes is used as a cathode substrate for obtaining a cathode current collector. An aqueous solution of ammonium dihydrogen phosphate is selected as a chemical conversion liquid to perform an anodizing treatment on the aluminum foil, and an anodized film (oxide layer) with a chemical conversion voltage of 2.0V is formed on the surface of the aluminum foil. The aluminum foil formed with the anodized film is immersed in an aqueous dispersion of a conductive polymer (PEDOT) to form a very thin conductive polymer layer on the anodized film. It should be noted that the conductive polymer layer formed by immersion is identified by a scanning electron microscope and is found to be so thin that the thickness cannot be measured, and therefore is not included in the thickness of the organic conductive layer of the present invention. The conductive polymer layer formed by immersion is used as a power supply layer, and electrolytic polymerization is carried out in the same manner as in Example 1. As an organic conductive layer, a PEDOT layer is formed on the power supply layer in the same manner as in Example 1 to obtain a cathode current collector. Thereafter, the same steps as in Example 1 are repeated. It should be noted that the organic conductive layer after the capacitor element is manufactured (after the solid electrolyte layer is formed, the same applies hereinafter) is provided in close contact with the oxide layer formed by the anodic oxide film.
[0176] <Example 3>
[0177] The same steps as in Example 1 were performed except that the time of the first stage was set to 7.5 seconds for the constant current electrolytic polymerization. It should be noted that the organic conductive layer in the cathode collector of Example 3 is a PEDOT layer having a dense layer with a thickness of 0.01 μm and a porous layer with a thickness of 10.0 μm and a porosity of 0.47. In addition, the organic conductive layer after the capacitor element is made is closely arranged on the inorganic conductive layer, and its thickness is 5.4 μm.
[0178] <Example 4>
[0179] The same steps as in Example 1 were performed except that the time of the first stage was set to 22.5 seconds for the constant current electrolytic polymerization. It should be noted that the organic conductive layer in the cathode current collector of Example 4 is a PEDOT layer having a dense layer with a thickness of 0.03 μm and a porous layer with a thickness of 10.0 μm and a porosity of 0.47. In addition, the organic conductive layer after the capacitor element is made is closely arranged on the inorganic conductive layer, and its thickness is 5.4 μm.
[0180] <Example 5>
[0181] The same steps as in Example 1 were performed except that the time of the first stage was set to 25 minutes for the constant current electrolytic polymerization. It should be noted that the organic conductive layer in the cathode current collector of Example 5 is a PEDOT layer having a dense layer with a thickness of 2.0 μm and a porous layer with a thickness of 10.0 μm and a porosity of 0.46. In addition, the organic conductive layer after the capacitor element is made is closely arranged on the inorganic conductive layer, and its thickness is 7.4 μm.
[0182] <Example 6>
[0183] The same steps as in Example 1 were performed except that the time of the first stage was set to 37.5 minutes for the constant current electrolytic polymerization. It should be noted that the organic conductive layer in the cathode current collector of Example 6 is a PEDOT layer having a dense layer with a thickness of 3.0 μm and a porous layer with a thickness of 10.0 μm and a porosity of 0.46. In addition, the organic conductive layer after the capacitor element is made is closely arranged on the inorganic conductive layer, and its thickness is 8.4 μm.
[0184] <Example 7>
[0185] The same steps as in Example 1 were performed except that the time of the first stage was set to 175 minutes and the time of the second stage was set to 2.9 minutes for the constant current electrolytic polymerization, and that the drying after washing with water was performed at 50°C for 120 minutes. It should be noted that the organic conductive layer in the cathode collector of Example 7 is a PEDOT layer having a dense layer with a thickness of 14 μm and a porous layer with a thickness of 2.0 μm and a porosity of 0.60. In addition, the organic conductive layer after making the capacitor element is closely arranged on the inorganic conductive layer, and its thickness is 14.8 μm.
[0186] <Example 8>
[0187] The same steps as in Example 7 were performed except that the time of the first stage was set to 200 minutes for the constant current electrolytic polymerization. It should be noted that the organic conductive layer in the cathode current collector of Example 8 is a PEDOT layer having a dense layer with a thickness of 16 μm and a porous layer with a thickness of 2.0 μm and a porosity of 0.60. In addition, the organic conductive layer after the capacitor element is made is closely arranged on the inorganic conductive layer, and its thickness is 16.8 μm.
[0188] <Example 9>
[0189] Except for the constant current electrolytic polymerization, it is not a two-stage process but a one-stage process at 0.1 mA / cm 2 The same steps as in Example 1 were performed except that the electrolytic polymerization step was performed under the conditions of 26.3 minutes. It should be noted that the organic conductive layer in the cathode current collector of Example 9 is a PEDOT layer having a dense layer thickness of 2.1 μm. In addition, the organic conductive layer after the capacitor element is made is closely arranged on the inorganic conductive layer, and its thickness is 2.1 μm.
[0190] <Example 10>
[0191] The same steps as in Example 9 were performed except that the time for constant current electrolytic polymerization was set to 31.3 minutes. It should be noted that the organic conductive layer in the cathode current collector of Example 10 was a PEDOT layer having a dense layer thickness of 2.5 μm. In addition, the organic conductive layer after the capacitor element was made was closely attached to the inorganic conductive layer, and its thickness was 2.5 μm.
[0192] <Example 11>
[0193] The same steps as in Example 9 were performed except that the time for constant current electrolytic polymerization was set to 175 minutes. It should be noted that the organic conductive layer in the cathode current collector of Example 11 was a PEDOT layer having a dense layer thickness of 14 μm. In addition, the organic conductive layer after the capacitor element was made was closely attached to the inorganic conductive layer, and its thickness was 14 μm.
[0194] <Example 12>
[0195] The same steps as in Example 9 were performed except that the time for constant current electrolytic polymerization was set to 200 minutes. It should be noted that the organic conductive layer in the cathode collector of Example 12 was a PEDOT layer having a dense layer thickness of 16 μm. In addition, the organic conductive layer after the capacitor element was made was closely attached to the inorganic conductive layer, and its thickness was 16 μm.
[0196] <Example 13>
[0197] The same steps as in Example 9 were performed except that the time for constant current electrolytic polymerization was set to 271 minutes. It should be noted that the organic conductive layer in the cathode current collector of Example 13 was a PEDOT layer having a dense layer thickness of 21.7 μm. In addition, the organic conductive layer after the capacitor element was made was closely arranged on the inorganic conductive layer, and its thickness was 21.7 μm.
[0198] <Example 14>
[0199] The same steps as in Example 1 were performed except that the time of the first stage was set to 25 minutes and the time of the second stage was set to 2.7 minutes for the constant current electrolytic polymerization. It should be noted that the organic conductive layer in the cathode current collector of Example 14 is a PEDOT layer having a dense layer with a thickness of 2.0 μm and a porous layer with a thickness of 1.9 μm and a porosity of 0.46. In addition, the organic conductive layer after the capacitor element is made is closely arranged on the inorganic conductive layer, and its thickness is 3.0 μm.
[0200] <Example 15>
[0201] The same steps as in Example 14 were performed except that the time of the second stage was set to 3.6 minutes for the constant current electrolytic polymerization. It should be noted that the organic conductive layer in the cathode current collector of Example 15 is a PEDOT layer having a dense layer with a thickness of 2.0 μm and a porous layer with a thickness of 2.5 μm and a porosity of 0.46. In addition, after the capacitor element is made, the thickness of the organic conductive layer closely attached to the inorganic conductive layer is 3.4 μm.
[0202] <Example 16>
[0203] The same steps as in Example 1 were performed except that the time of the first stage was set to 6.3 minutes and the time of the second stage was set to 15.7 minutes for the constant current electrolytic polymerization. It should be noted that the organic conductive layer in the cathode collector of Example 16 is a PEDOT layer having a dense layer with a thickness of 0.5 μm and a porous layer with a thickness of 11.0 μm and a porosity of 0.46. In addition, the organic conductive layer after the capacitor element is made is closely arranged on the inorganic conductive layer, and its thickness is 6.5 μm.
[0204] <Example 17>
[0205] The same steps as in Example 16 were performed except that the time of the second stage was set to 18.6 minutes for the constant current electrolytic polymerization. It should be noted that the organic conductive layer in the cathode current collector of Example 17 is a PEDOT layer having a dense layer with a thickness of 0.5 μm and a porous layer with a thickness of 13.0 μm and a porosity of 0.46. In addition, the organic conductive layer after the capacitor element is made is closely arranged on the inorganic conductive layer, and its thickness is 7.6 μm.
[0206] <Example 18>
[0207] The same steps as in Example 16 were performed except that the time of the second stage was set to 34.3 minutes for the constant current electrolytic polymerization. It should be noted that the organic conductive layer in the cathode current collector of Example 18 is a PEDOT layer having a dense layer with a thickness of 0.5 μm and a porous layer with a thickness of 24.0 μm and a porosity of 0.46. In addition, the organic conductive layer after the capacitor element is made is closely arranged on the inorganic conductive layer, and its thickness is 13.5 μm.
[0208] <Example 19>
[0209] The same steps as in Example 16 were performed except that the time of the second stage was set to 37.1 minutes for the constant current electrolytic polymerization. It should be noted that the organic conductive layer in the cathode current collector of Example 19 is a PEDOT layer having a dense layer with a thickness of 0.5 μm and a porous layer with a thickness of 26.0 μm and a porosity of 0.46. In addition, the organic conductive layer after the capacitor element is made is closely arranged on the inorganic conductive layer, and its thickness is 14.6 μm.
[0210] <Example 20>
[0211] The same steps as in Example 1 were performed except that the time of the first stage of the constant current electrolytic polymerization was set to 6.3 minutes and that the drying after washing with water was performed at 30°C for 120 minutes. It should be noted that the organic conductive layer in the cathode current collector of Example 20 is a PEDOT layer having a dense layer with a thickness of 0.5 μm and a porous layer with a thickness of 10.0 μm and a porosity of 0.80. In addition, the organic conductive layer after the capacitor element is made is closely arranged on the inorganic conductive layer, and its thickness is 2.5 μm.
[0212] <Example 21>
[0213] The same steps as in Example 1 were performed except that the drying was performed after washing at 40°C for 120 minutes. It should be noted that the organic conductive layer in the cathode current collector of Example 21 is a PEDOT layer having a dense layer with a thickness of 0.2 μm and a porous layer with a thickness of 10.0 μm and a porosity of 0.70. In addition, the organic conductive layer after the capacitor element is made is closely arranged on the inorganic conductive layer, and its thickness is 3.2 μm.
[0214] <Example 22>
[0215] The same steps as in Example 21 were performed except that the drying temperature after washing was set to 50°C. It should be noted that the organic conductive layer in the cathode current collector of Example 22 was a PEDOT layer having a dense layer with a thickness of 0.2 μm and a porous layer with a thickness of 10.0 μm and a porosity of 0.60. In addition, the organic conductive layer after the capacitor element was made was closely attached to the inorganic conductive layer and had a thickness of 4.2 μm.
[0216] <Example 23>
[0217] The same steps as in Example 1 were performed except that the drying temperature after washing was set to 120°C. It should be noted that the organic conductive layer in the cathode current collector of Example 23 was a PEDOT layer having a dense layer with a thickness of 0.2 μm and a porous layer with a thickness of 10.0 μm and a porosity of 0.31. In addition, the organic conductive layer after the capacitor element was made was closely attached to the inorganic conductive layer and had a thickness of 7.1 μm.
[0218] <Example 24>
[0219] The same steps as in Example 1 were performed except that the drying temperature after washing was set to 150°C. It should be noted that the organic conductive layer in the cathode current collector of Example 24 was a PEDOT layer having a dense layer with a thickness of 0.2 μm and a porous layer with a thickness of 10.0 μm and a porosity of 0.14. In addition, the organic conductive layer after the capacitor element was made was closely attached to the inorganic conductive layer and had a thickness of 8.8 μm.
[0220] <Example 25>
[0221] The same steps as in Example 1 were performed except that the drying temperature after washing was set to 160°C. It should be noted that the organic conductive layer in the cathode current collector of Example 25 was a PEDOT layer having a dense layer with a thickness of 0.2 μm and a porous layer with a thickness of 10.0 μm and a porosity of 0.05. In addition, the organic conductive layer after the capacitor element was made was closely attached to the inorganic conductive layer and had a thickness of 9.7 μm.
[0222] <Example 26>
[0223] The same steps as in Example 1 were performed except that pyrrole was used as the monomer contained in the electrolytic polymerization solution instead of 3,4-ethylenedioxythiophene (EDOT). It should be noted that the organic conductive layer in the cathode current collector of Example 26 is a PPY (polypyrrole) layer having a dense layer with a thickness of 2.0 μm and a porous layer with a thickness of 10.0 μm and a porosity of 0.46. In addition, the organic conductive layer after making the capacitor element is closely arranged on the inorganic conductive layer, and its thickness is 5.6 μm.
[0224] <Comparative Example 1>
[0225] The same procedure as in Example 1 was performed except that the electrolytic polymerization was not performed.
[0226] <Comparative Example 2>
[0227] The same procedure as in Example 2 was performed except that the electrolytic polymerization was not performed.
[0228] <Comparative Example 3>
[0229] The same steps as in Example 9 were performed except that the time for constant current electrolytic polymerization was set to 2.5 minutes. It should be noted that the organic conductive layer in the cathode collector of Comparative Example 3 was a PEDOT layer having only a dense layer with a thickness of 0.2 μm. In addition, the organic conductive layer after the capacitor element was made was closely attached to the inorganic conductive layer, and its thickness was 0.2 μm.
[0230] <Comparative Example 4>
[0231] The same steps as in Example 9 were performed except that the time for constant current electrolytic polymerization was set to 21.3 minutes. It should be noted that the organic conductive layer in the cathode collector of Comparative Example 4 was a PEDOT layer having a dense layer thickness of 1.7 μm. In addition, the organic conductive layer after the capacitor element was made was closely attached to the inorganic conductive layer, and its thickness was 1.7 μm.
[0232] <Comparative Example 5>
[0233] The same steps as in Example 9 were performed except that the time for constant current electrolytic polymerization was set to 289 minutes. It should be noted that the organic conductive layer in the cathode collector of Comparative Example 5 was a PEDOT layer having a dense layer thickness of 23.1 μm. In addition, the organic conductive layer after the capacitor element was made was closely arranged on the inorganic conductive layer, and its thickness was 23.1 μm.
[0234] <Example 27>
[0235] (1) Fabrication of solid electrolytic capacitors
[0236] The capacitor element with a solid electrolyte layer obtained by the same procedure as in Example 1 was sealed in an outer case and aged at 125° C. for 45 minutes with a voltage of 25 V applied to obtain a solid electrolytic capacitor with a rated voltage of 25 V.
[0237] (2) Evaluation of capacitor characteristics
[0238] As initial characteristics of the obtained capacitor, ESR at 100 kHz was measured at 20° C. Then, after being left at a high temperature of 125° C. for 2000 hours as a durability test, ESR at 100 kHz was measured again as characteristics after the durability test.
[0239] <Example 28>
[0240] The capacitor element with a solid electrolyte layer added thereto, obtained by the same procedure as in Example 2, was sealed in an outer case.
[0241] Thereafter, the same steps as in Example 27 were performed.
[0242] <Comparative Example 6>
[0243] The same procedure as in Example 27 was performed except that the electrolytic polymerization was not performed.
[0244] <Comparative Example 7>
[0245] The same procedure as in Example 28 was performed except that the electrolytic polymerization was not performed.
[0246]
Table 1
[0247] Table 1. 100kHz ESR of 35WV hybrid electrolytic capacitor before and after 125℃ heat test
[0248]
[0249] ※ Regarding the initial value of 100kHz ESR and the rate of change after the endurance test, the values of each example and comparative example are shown, with the value of comparative example 1 being taken as 100.
[0250]
Table 2
[0251] 2. 100kHz ESR of 25WV solid electrolytic capacitor before and after 125℃ heat resistance test
[0252]
[0253] ※ The initial value of 100kHz ESR and the rate of change after the endurance test are shown with the value of Comparative Example 6 as 100.
[0254] (A) Test results of hybrid electrolytic capacitors in Table 1
[0255] All of the hybrid electrolytic capacitors produced in the examples in Table 1 had lower initial ESR values and lower ESR change rates after the heat resistance test than the comparative examples.
[0256] First, the cathode current collector excluding the organic conductive layer will be described.
[0257] The surface state of the cathode substrate, the structure of the oxide layer, and the presence or absence of an inorganic conductive layer can be discussed by comparing Example 1 and Example 2. In Example 1, the surface of the cathode substrate is smooth, the oxide layer is formed by a natural oxide film, and an inorganic conductive layer is formed. In Example 2, the surface of the cathode substrate is rough due to the formation of etching holes, the oxide layer is formed by a natural oxide film, and no inorganic conductive layer is formed. Then, the initial ESR value and the ESR change rate are 53 and 29 in Example 1, and 59 and 32 in Example 2. Compared with Example 2, the initial ESR value and the ESR change rate of Example 1 are both suppressed to be lower. Therefore, in addition to the organic conductive layer in the cathode collector, it is preferred that the surface of the cathode substrate is smooth, the oxide layer is formed by a natural oxide film, and an inorganic conductive layer is formed.
[0258] Next, a description will be given of a case where the organic conductive layer of the cathode current collector before the capacitor element is produced (before being incorporated into the capacitor element) is formed of a dense layer and a porous layer.
[0259] The situation that the organic conductive layer is formed by a dense layer and a porous layer can be discussed by comparing Example 1 with Comparative Examples 1 and 3. In Example 1, a porous layer (thickness: 10 μm, porosity: 0.46) is formed after a dense layer with a thickness of 0.2 μm is formed in the same manner as in Comparative Example 3. In addition, Comparative Example 1 has the same structure as Example 1 and Comparative Example 3 except that an organic conductive layer is not formed. Then, the initial ESR value and the ESR change rate are 53 and 29 for Example 1, 96 and 95 for Comparative Example 3, and 100 and 100 for Comparative Example 1. Compared with Comparative Examples 1 and 3, the initial ESR value and the ESR change rate of Example 1 are both suppressed to be lower. It can be seen that by forming an organic conductive layer composed of a dense layer and a porous layer, the initial ESR value and the ESR change rate are suppressed to be lower.
[0260] In the discussion of changing the thickness of the dense layer, the thickness of the dense layer becomes thicker in the order of Example 3 (0.01 μm), Example 4 (0.03 μm), Example 1 (0.2 μm), Example 5 (2 μm), Example 6 (3 μm), Example 7 (14 μm), and Example 8 (16 μm). Then, in Example 1 and Examples 4 to 7 where the thickness of the dense layer is greater than 0.02 μm and less than 15 μm, the initial ESR value is less than 61 and the ESR change rate is less than 33. Compared with the initial ESR value of 68 and the ESR change rate of 49 in Example 3 where the thickness of the dense layer is 0.01 μm, the initial value and the change rate are suppressed to be lower. It can be seen that when the thickness of the dense layer is less than 0.02 μm, the penetration of the dispersion liquid cannot be fully suppressed, the adhesion between the cathode substrate and the organic conductive layer is problematic, and the initial ESR value and the ESR change rate become larger. On the other hand, in Example 8, in which the thickness of the dense layer is 16 μm, the initial ESR value is suppressed to be lower than that of the comparative example, and the ESR change rate is slightly higher than that of other examples. It can be seen that when the thickness of the dense layer is 15 μm or more, due to the different thermal expansion coefficients of the cathode substrate and the organic conductive layer, the peeling of the organic conductive layer caused by stress under the action of the long-term heat load of use becomes a problem, and as a result, the ESR change rate becomes higher. In addition, in Examples 6 and 7 in which the thickness of the dense layer is 3 μm and 14 μm, respectively, although there is no problem with the characteristics, in the case where the organic conductive layer is formed by a dense layer and a porous layer, the porous layer that can make the film thicker with higher manufacturing efficiency and shorter time is formed to be thicker, which is more preferred in manufacturing. Based on the viewpoint of the manufacturing process, the film thickness of the dense layer is preferably thinner. Therefore, it can be seen that the thickness of the dense layer is preferably less than 2.5 μm. According to the above, the thickness of the dense layer is preferably 0.02 μm or more and less than 15 μm, and more preferably 0.02 μm or more and less than 2.5 μm.
[0261] In the discussion of changing the thickness of the porous layer, the thickness of the porous layer becomes thicker in the order of Example 14 (1.9 μm), Example 15 (2.5 μm), Example 1 (10 μm), Example 16 (11 μm), Example 17 (13 μm), Example 18 (24 μm), and Example 19 (26 μm). Moreover, in Examples 1 and 15 to 18 where the thickness of the porous layer is between 2 μm and 25 μm, the ESR change rate is less than 33, which is suppressed to a lower level compared to the ESR change rate of 54 in Examples 14 and 19 where the thickness of the porous layer is 1.9 μm and 26 μm, respectively. On the other hand, in Examples 14 and 19 where the thickness of the porous layer is 1.9 μm and 26 μm, respectively, the ESR change rate is suppressed to a lower level compared to the comparative example, and the ESR change rate is slightly higher than that of the other examples. It can be seen from this that when the thickness of the porous layer is thinner than 2 μm, a sufficient anchoring effect with the solid electrolyte layer is not obtained. In addition, when the thickness of the porous layer is thicker than 25 μm, the residue of the electrolyte used for electrolytic polymerization, which will have an adverse effect on ESR, is difficult to completely remove from the pores of the porous layer. In addition, although there is no problem with the ESR change rate, in Examples 17 and 18 where the thickness of the porous layer is 12 μm to 25 μm, although the anchoring effect with the solid electrolyte layer does not change, the manufacturing process of cleaning the residue of the electrolyte in the porous layer becomes longer. Based on the above, it can be seen that the thickness of the porous layer is preferably 2 μm to 25 μm, and more preferably 2 μm to 12 μm.
[0262] In the discussion of changing the porosity, the porosity becomes lower in the order of Example 20 (0.8), Example 21 (0.7), Example 22 (0.6), Example 1 (0.46), Example 23 (0.31), Example 24 (0.14), and Example 25 (0.05), that is, the porosity becomes lower. Moreover, in Example 1 and 21 to 24 where the porosity is 0.1 to 0.7, the ESR change rate is 41 or less, which is suppressed to a lower level compared to the ESR change rates of 51 and 52 of Examples 20 and 25 where the porosity is 0.8 and 0.05, respectively. In addition, in Examples 1 and 21 to 23 where the porosity is 0.3 to 0.7, the ESR change rate is suppressed to a particularly low level (below 31). Based on the above, it can be seen that the porosity is preferably 0.1 to 0.7, and more preferably 0.3 to 0.7.
[0263] As can be seen from the above, the structure of the organic conductive layer can suppress the ESR initial value and the ESR change rate to be low by selecting a structure consisting of a dense layer and a porous layer formed thereon.
[0264] By selecting a dense layer with a thickness of not less than 0.02μm and not more than 15μm, sufficient contact with the substrate can be ensured. By selecting a porous layer with a porosity of not less than 0.1 and not more than 0.7 and a thickness of not less than 2μm and not more than 25μm, a sufficient anchoring effect with the solid electrolyte layer can be obtained. In particular, the initial ESR value and the ESR change rate can be suppressed to a low level, and the close adhesion between the cathode collector and the solid electrolyte layer when loaded can be well ensured.
[0265] It should be noted that the dense layer is preferably a certain thickness or more in order to ensure the contact with the layer on the cathode substrate 1 side. Since the manufacturing process is long, the dense layer is as thin as possible, the manufacturing efficiency is high, and the porous layer that can form a thicker organic conductive layer in a short time is preferably formed thicker. The porous layer requires sufficient thickness to obtain an anchoring effect, and also requires sufficient thickness to suppress the penetration of the electrolyte in the capacitor element, but it is preferably within the film thickness range that is easy to remove the electrolyte residue in the porous layer by cleaning. In addition, with regard to porosity, it is preferably a porosity with high adhesion to the dense layer and sufficient anchoring effect can also be obtained with the solid electrolyte layer. According to the above, as an example of the most suitable combination of a dense layer and a porous layer, the following situations can be cited: the thickness of the dense layer is 0.02 μm or more and 0.5 μm or less, the thickness of the porous layer is 3 μm or more and 12 μm or less, and the porosity is 0.3 or more and 0.7 or less.
[0266] In Example 26, pyrrole is electrolytically polymerized as a monomer instead of EDOT to form an organic conductive layer. Among the examples, the geometric structures of the organic conductive layers of Examples 1 and 26 are relatively similar. By comparing them, it is found that the ESR change rate after the heat resistance test of Example 1 having a PEDOT layer is suppressed to be lower. Based on the above, it can be seen that the component of the organic conductive layer is preferably PEDOT.
[0267] Next, a description will be given of a case where the organic conductive layer of the cathode current collector before the capacitor element is produced is formed of a dense layer and has a predetermined thickness.
[0268] In the study of changing the thickness of the organic conductive layer (only the dense layer), the thickness of the dense layer became thicker in the order of Comparative Example 3 (0.2 μm), Comparative Example 4 (1.7 μm), Example 9 (2.1 μm), Example 10 (2.5 μm), Example 11 (14 μm), Example 12 (16 μm), Example 13 (21.7 μm), and Comparative Example 5 (23.1 μm). In addition, in Examples 9 to 13 where the thickness of the organic conductive layer was greater than 2 μm and less than 22 μm, the initial ESR value was less than 70, which was suppressed to a lower value compared to the initial ESR value of 84 or more in Comparative Examples 3 to 5 where the thickness of the dense layer was less than 2 μm or greater than 22 μm. It can be seen that if the organic conductive layer is formed by a dense layer and the thickness of the organic conductive layer is less than 2 μm, the penetration of the electrolyte cannot be fully suppressed, and the inorganic conductive layer (in the above-mentioned embodiments, all inorganic conductive layers are formed, and in the case where no inorganic conductive layer is formed, it is an oxide layer) and the organic conductive layer are not sufficiently adhered. In addition, it can be seen that when the thickness is greater than 22 μm, the distance between the cathode substrate and the anode substrate becomes too long, and the effect of the increase in ESR cannot be ignored.
[0269] Furthermore, in the above-mentioned examples, the initial ESR value (70) of Example 9 (2.1 μm) is relatively high. This shows that if the thickness of the organic conductive layer is thinner than 2.5 μm, the permeation of the electrolyte over time cannot be sufficiently suppressed even when left at room temperature without load.
[0270] In addition, in Examples 12 and 13 where the thickness of the organic conductive layer is greater than 15 μm, there is no problem with the initial ESR value, but the ESR change rate is slightly higher than that of the other Examples. This shows that due to the different thermal expansion coefficients of the cathode substrate and the organic conductive layer, the stress caused by the long-term heat load during use causes peeling of the organic conductive layer, which results in an increase in ESR.
[0271] As can be seen from the above, when the organic conductive layer is formed of a dense layer, the thickness of the organic conductive layer is greater than 2 μm and less than 22 μm, and preferably greater than 2.5 μm and less than 15 μm.
[0272] In Comparative Examples 3 and 4, similarly to Patent Document 2, only a dense layer is formed on the surface of the inorganic conductive layer as an organic conductive layer, and the dense layer has a thickness within the range disclosed in Patent Document 2. In Examples 1, 3 to 8 and 14 to 26, in which a porous layer is also formed on the surface of the dense layer as an organic conductive layer, the initial ESR value and the ESR change rate after the heat resistance test are suppressed to be lower than those in Comparative Examples 3 and 4. In addition, in Examples 9 to 13, in which only a dense layer having a thickness in the range of greater than 2 μm and less than 22 μm is formed as an organic conductive layer, the initial ESR value and the ESR change rate after the heat resistance test are suppressed to be lower than those in Comparative Examples 3 and 4.
[0273] According to the above, the present invention of forming the organic conductive layer in the cathode collector before the capacitor element is made by a dense layer and a porous layer provided on the surface of the dense layer, further improves the adhesion in the cathode collector (the adhesion of the oxide layer or inorganic conductive layer and the organic conductive layer) and the adhesion of the cathode collector and the solid electrolyte layer, so that the problem of contact resistance can be solved. In addition, the present invention of forming the organic conductive layer in the cathode collector before the capacitor element is made by a dense layer and making its thickness greater than 2μm and less than 22μm, further improves the adhesion in the cathode collector (the adhesion of the oxide layer or inorganic conductive layer and the organic conductive layer), so that the problem of contact resistance can be solved.
[0274] Next, the organic conductive layer in the electrolytic capacitor after the capacitor element is produced will be described.
[0275] Pay attention to the thickness of the organic conductive layer. Compared with Examples 1 and 3 to 25, the initial ESR value and the ESR change rate after the heat resistance test are larger for Comparative Examples 3 and 4 thinner than 2μm and Comparative Example 5 thicker than 22μm. In addition, Example 9 thinner than 2.5μm and Examples 8, 12 and 13 thicker than 15μm have a larger ESR change rate than the other embodiments mentioned above. In the embodiments above 2.5μm and below 15μm, the initial ESR value and the ESR change rate are suppressed to be particularly low. It can be seen that based on the same reasons as the results of Examples 9 to 13 and Comparative Examples 3 and 4, in which the organic conductive layer before the capacitor element is made is only a dense layer, the thickness of the organic conductive layer in the electrolytic capacitor can be greater than 2μm and less than 22μm, and more preferably greater than 2.5μm and less than 15μm.
[0276] (B) Test results of solid electrolytic capacitors in Table 2
[0277] Compared with the comparative example in Table 2, the ESR initial value and the ESR change rate after the heat resistance test of the example in Table 2 are suppressed to be low.
[0278] It can be seen that similarly to the case where the organic conductive layer in the results related to the hybrid electrolytic capacitor of (A) is composed of a dense layer and a porous layer, in the solid electrolytic capacitor, in the organic conductive layer obtained in the embodiment, in addition to forming a dense layer on the side in contact with the oxide layer or the inorganic conductive layer, a porous layer is also formed on the side in contact with the solid electrolyte layer, so the tightness inside the cathode collector and the tightness between the cathode collector and the solid electrolyte layer are improved, low ESR is achieved, and the ESR change rate after the heat resistance test is also suppressed to a low level.
[0279] Possibility of industrial application
[0280] The present invention can be used in an electrolytic capacitor using at least a solid electrolyte containing a conductive polymer as an electrolyte component.
[0281] [Remark]
[0282] The present disclosure discloses the following structures.
[0283] [Structure 1]
[0284] A cathode current collector, characterized in that it comprises: a cathode substrate formed of a valve metal; an oxide layer formed of an oxide of the valve metal arranged on the surface of the cathode substrate; and an organic conductive layer containing a conductive polymer arranged on the surface of the oxide layer, wherein the organic conductive layer is composed of a dense layer arranged on the surface of the oxide layer and a porous layer arranged on the surface of the dense layer.
[0285] [Structure 2]
[0286] In the cathode current collector as described in Structure 1, an inorganic conductive layer containing an inorganic conductive material is further provided between the oxide layer and the organic conductive layer, and the dense layer is provided on the surface of the inorganic conductive layer.
[0287] [Structure 3]
[0288] The cathode current collector as described in Structure 1 or 2, wherein the surface of the cathode substrate is smooth.
[0289] [Structure 4]
[0290] The cathode current collector according to any one of Structures 1 to 3, wherein the thickness of the porous layer is 2 μm or more and 25 μm or less.
[0291] [Structure 5]
[0292] The cathode current collector according to any one of Structures 1 to 4, wherein the dense layer has a thickness of 0.02 μm or more and less than 15 μm.
[0293] [Structure 6]
[0294] The cathode current collector according to any one of Structures 1 to 5, wherein the porosity of the porous layer is 0.1 or more and 0.7 or less.
[0295] [Structure 7]
[0296] The cathode current collector as described in any one of Structures 1 to 6, wherein the organic conductive layer is an electrolytic polymer film.
[0297] [Structure 8]
[0298] The electrolytic capacitor according to any one of Structures 1 to 7, wherein the conductive polymer is poly(3,4-ethylenedioxythiophene).
[0299] [Structure 9]
[0300] A cathode current collector, characterized in that it comprises: a cathode substrate formed of a valve metal; an oxide layer formed of an oxide of the valve metal arranged on the surface of the cathode substrate; and an organic conductive layer containing a conductive polymer arranged on the surface of the oxide layer, wherein the organic conductive layer is composed of a dense layer arranged on the surface of the oxide layer, and the thickness of the organic conductive layer is greater than 2 μm and less than 22 μm.
[0301] [Structure 10]
[0302] In the cathode current collector as described in Structure 9, an inorganic conductive layer containing an inorganic conductive material is further provided between the oxide layer and the organic conductive layer, and the dense layer is provided on the surface of the inorganic conductive layer.
[0303] [Structure 11]
[0304] The cathode current collector as described in Structure 9 or 10, wherein the surface of the cathode substrate is smooth.
[0305] [Structure 12]
[0306] The cathode current collector as described in any one of Structures 9 to 11, wherein the organic conductive layer is an electrolytic polymer film.
[0307] [Structure 13]
[0308] The electrolytic capacitor according to any one of Structures 9 to 12, wherein the conductive polymer is poly(3,4-ethylenedioxythiophene).
[0309] [Structure 14]
[0310] An electrolytic capacitor contains at least a solid electrolyte as an electrolyte component and uses the cathode current collector according to any one of Structures 1 to 13.
[0311] [Structure 15]
[0312] The electrolytic capacitor according to Structure 14 further contains an electrolyte solution as an electrolyte component.
[0313] [Structure 16]
[0314] An electrolytic capacitor having:
[0315] A cathode current collector comprising: a cathode substrate formed of a valve metal; an oxide layer formed of an oxide of the valve metal disposed on a surface of the cathode substrate; and an organic conductive layer containing a conductive polymer disposed on a surface of the oxide layer, and
[0316] at least a solid electrolyte as an electrolyte component,
[0317] The method is characterized in that the organic conductive layer is closely arranged on the surface of the oxide layer, and the thickness of the organic conductive layer is greater than 2 μm and less than 22 μm.
[0318] [Structure 17]
[0319] In the electrolytic capacitor according to Structure 16, an inorganic conductive layer including an inorganic conductive material is further provided between the oxide layer and the organic conductive layer, and the organic conductive layer is provided in close contact with a surface of the inorganic conductive layer.
[0320] [Structure 18]
[0321] The electrolytic capacitor according to Structure 16 or 17, wherein the surface of the cathode substrate is smooth.
[0322] [Structure 19]
[0323] The electrolytic capacitor according to any one of Structures 16 to 18, wherein the organic conductive layer is an electrolytic polymer film.
[0324] [Structure 20]
[0325] The electrolytic capacitor according to any one of Structures 16 to 19, wherein the conductive polymer is poly(3,4-ethylenedioxythiophene).
[0326] [Structure 21]
[0327] The electrolytic capacitor according to any one of Structures 16 to 20 further contains an electrolyte solution as an electrolyte component.
[0328] Description of Reference Numerals
[0329] 1 Cathode substrate
[0330] 2 Oxide layer
[0331] 3 Inorganic conductive layer
[0332] 4 Dense layer
[0333] 5 Porous layer
[0334] 6, 9, 11 Organic conductive layer
[0335] 7, 8, 10, 12 Cathode current collector
Claims
1. A cathode current collector, It is characterized in that The invention comprises: a cathode substrate formed of a valve metal; an oxide layer formed of an oxide of the valve metal arranged on the surface of the cathode substrate; and an organic conductive layer containing a conductive polymer arranged on the surface of the oxide layer, wherein the organic conductive layer is composed of a dense layer arranged on the surface of the oxide layer and a porous layer arranged on the surface of the dense layer.
2. A cathode current collector, It is characterized in that The invention comprises: a cathode substrate formed of a valve metal; an oxide layer formed of an oxide of the valve metal arranged on the surface of the cathode substrate; and an organic conductive layer containing a conductive polymer arranged on the surface of the oxide layer, wherein the organic conductive layer is composed of a dense layer arranged on the surface of the oxide layer, and the thickness of the organic conductive layer is greater than 2 μm and less than 22 μm.
3. The cathode current collector according to claim 1 or 2, in, An inorganic conductive layer including an inorganic conductive material is further provided between the oxide layer and the organic conductive layer, and the dense layer is provided on the surface of the inorganic conductive layer.
4. The cathode current collector according to claim 1 or 2, in, The surface of the cathode substrate is smooth.
5. The cathode current collector according to claim 1, in, The thickness of the porous layer is 2 μm or more and 25 μm or less.
6. The cathode current collector according to claim 1, in, The dense layer has a thickness of 0.02 μm or more and less than 15 μm.
7. The cathode current collector according to claim 1, in, The porosity of the porous layer is 0.1 or more and 0.7 or less.
8. The cathode current collector according to claim 1 or 2, in, The organic conductive layer is an electrolytic polymer film.
9. The cathode current collector according to claim 1 or 2, in, The conductive polymer is poly(3,4-ethylenedioxythiophene).
10. An electrolytic capacitor comprising at least a solid electrolyte as an electrolyte component and using the cathode current collector according to claim 1 or 2.
11. The electrolytic capacitor according to claim 10, in, It also contains an electrolyte solution as an electrolyte component.
12. An electrolytic capacitor comprising: A cathode current collector comprising: a cathode substrate formed of a valve metal; an oxide layer formed of an oxide of the valve metal disposed on a surface of the cathode substrate; and an organic conductive layer containing a conductive polymer disposed on a surface of the oxide layer, and at least a solid electrolyte as an electrolyte component, It is characterized in that The organic conductive layer is closely disposed on the surface of the oxide layer, and the thickness of the organic conductive layer is greater than 2 μm and less than 22 μm.
13. The electrolytic capacitor according to claim 12, in, An inorganic conductive layer including an inorganic conductive material is further provided between the oxide layer and the organic conductive layer, and the organic conductive layer is provided in close contact with the surface of the inorganic conductive layer.
14. The electrolytic capacitor according to claim 12, in, The surface of the cathode substrate is smooth.
15. The electrolytic capacitor according to claim 12, in, The organic conductive layer is an electrolytic polymer film.
16. The electrolytic capacitor according to claim 12, in, The conductive polymer is poly(3,4-ethylenedioxythiophene).
17. The electrolytic capacitor according to claim 12, in, It also contains an electrolyte solution as an electrolyte component.
